Functional characterization of CnAGAL2, a key α-galactosidase involved in postharvest endosperm thickening of coconut (Cocos nucifera L.) - Jian Wang; Fan-jing Zhang; Fang Liu; Yu-ping Man; Shi-biao Liu; Yan-chang Wang; Dong-dong Li (Postharvest Biology and Technology, 2026)

lnc5714 participates in silkworm resistance to Nosema bombycis infection by regulating MRPL4-related host energy metabolism - Li Sui; Qiong Yu; Wangbin Qin; Yujia Fang; Pingyang Wang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Invertebrate Pathology, 2026)

A morphometric framework for Danxia landform classification incorporating cliff characteristics - Hui Chen; Ping Zhou; Fang Chen; Hongwei Li; Jongmin Byun; Ping Yan; Sha Lei; Xinmin Zhou (Geomorphology, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

Boosting lattice oxygen activation and active sites generation via an Mn-O electron bridge for efficient simultaneous oxidation of toluene and NO over Mn5Co4Ce3Ox catalyst - Lei Gao; Yukai Quan; Ping Fang; Dong Xie; Caiting Li; Cheng Sun; Jiahao Zhang; Ruotao Bai; Jingshuo Zhang (Fuel, 2026)

Viable lactic acid bacteria across the production-food-gut continuum: Multi-stress adaptation and robustness engineering - Jing Cui; Jiahui Li; Meijuan Ran; Qi Chen; Jiehong Fang; Jiankang Jiang; Qing Cao; Ping Li; Han Jiang; Qing Gu (Trends in Food Science & Technology, 2026)

Molybdenum-functionalized thiolated chitosan repurposes aqueous V(V) as an in situ PMS activator for simultaneous organic degradation and vanadium recovery - Yating Wu; Ting Xiang; Lei Zhang; Ping Gao; Lei Li; Chensi Shen; Fang Li; Juan Zhou (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Combined effects of microplastics and Pb on soil-tobacco systems revealed by soil microbiomics and metabolomics - Rong ZHAO; Zeyu ZUO; Ping CONG; Haibin LI; Mingwei LI; Yanna ZHAO; Fang ZUO; Jiao SUN; Yuhuan SUN; Guangjian XU; Xuebo ZHENG; Fayuan WANG (Pedosphere, 2026)

Anthraquinone‑modulated oxygen disproportionation enables highly selective singlet oxygen generation for pollutant degradation - Yu Luo; Chenqi Lu; Chuang Xiao; Lin Ding; Mengyuan Zhao; Lingling Liu; Longshuai Zhang; Xibao Li; Fang Deng; Xubiao Luo; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Calculation of hydrogeological parameters based on a high-flow long-duration water release test of multiple deep boreholes, Xiadian coalfield, North China - Fang Li; Rui Luo; Zhijia Yu; Wubin Gao; Jianggen He; Yu Ping; Shiyuan Tian; Zihan Wang; Tao Cheng; Colin G. Farquharson; Xinyi Wang (Hydrogeology Journal, 2026)

Stable isotope labeling LC–MS for profiling the amine submetabolome in a D-lactate treated cell model - Yue-Qiang Chen; Xiao-Xia Dong; Li Liu; Xiu-Ping Chen; Chen-Guo Feng; Li-Xing Zhan; Yue Su; Fang Zhang; Yin-Long Guo (Analytica Chimica Acta, 2026)

A AIE Probe for Visual Monitoring of Endogenous and Exogenous H2S and Food Freshness - Rongqi Wang; Si Chen; Yamin Li; Tuotuo Fang; Zhan-Bin Jin; Ting-Ting Wei; Jia-Ping Li; Hai-Xian Ren; Zi-Ao Zong; Na-Na Li (Journal of Fluorescence, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Genomic expansion of efflux pumps is associated with metal-antibiotic super-resistance in bacteria from mining environments - Sijia Chao; Ping Wen; Xiao-nan Wang; Jie-Liang Liang; Yu Fang; Ying Qin; Jian-wei Liao; Wen-sheng Shu; Xinzhu Yi; Jin-tian Li (Journal of Hazardous Materials, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Investigating the influence of BaTiO3 morphology on piezo-photocatalytic antibacterial synergy - Yan Wang; Ping Wang; Yijia Fang; Yuanxiao Wang; Huaying Liu; Huan Li; Xiaoning Tang (Journal of Environmental Chemical Engineering, 2026)

Strategic ultrasonic regulation of Saccharomyces cerevisiae fermentation for enhanced anthocyanin production and wine quality - Jiaqi Wang; Jianing Li; Jiming Li; Ping Wang; Guoli Cheng; Binsheng Wei; Tingting Ma; Yulin Fang; Xiangyu Sun (Food Research International, 2026)

Operation-resolved VOC emissions from electronics manufacturing: Implications for ozone formation, toxicity, and risk-oriented management - Jun Tao; Rui Xu; Zhisheng Zhang; Zijun Tang; Ping Fang; Leilei Fei; Zhihui Li; Zhihang Chen (Environmental Research, 2026)

Chemical constituents with chemotaxonomic significance from the whole plants of Chloranthus sessilifolius K.F.Wu - Xin-Yu Chen; Meng-Li He; Wan-Wan Yu; Yang Liu; Yong-Ming Luo; Ling-Ying Huang; Zhi-Ping Li; Fang-You Chen (Biochemical Systematics and Ecology, 2026)

Optimal combination of iron/magnesium salts and urea can promote the degradation rate of maize straw by catalyzing the rapid de-polymerization of lignin - Han Li; Yuan fang Zhou; Sen Zhao; Si hui Yan; Ding hua Jia; Yan ping Zhang; Xiang dong Yang; Juan Li (Biocatalysis and Agricultural Biotechnology, 2026)

Sedative effects and stress-alleviating capabilities of four dietary plant-derived compounds on Procambarus clarkii - Zihao Li; Xinyi Xie; Ziqian Sun; Zhaoxuan Zhu; Shuang Zhang; Xiaoyan Liang; Mengyu Teng; Haitang Wang; Xiuhong Liu; Ping Yang; Xingxing Fang (Veterinary Research Communications, 2026)

Mechanism of Lactococcus lactis L19 in alleviating high-carbohydrate diet–induced glucose and lipid metabolism disorders in northern snakehead (Channa argus) - Xia Guo; Jie Xu; Qiongya Fang; Xinyu Zhang; Ping Zhang; Zhiqiang Shen; Siqi Jiao; Yidi Kong; Min Li; Guiqin Wang (Fish Physiology and Biochemistry, 2026)

Osteopontin-driven TGF-β1 signaling via integrin αvβ3-NF-κB axis impairs NK cell function in head and neck squamous cell carcinoma - Zhe Shen; Xin Li; Shi Luo; Yuzhang Gao; Imadoudini Hassimi Safia; Jie Jiang; Xin Qi; Wei Huang; Yalan Liu; Xing Fang; Yaoyun Tang; Ping Wu (Apoptosis, 2026)

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

New cutting tool wear testing method for evaluating the influence of foam additive on plowing effect during shield TBM tunnelling in dense sandy gravel ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Yu-Cong Pan; Wei-Qiang Xie; Xin-Fang Li; Hao-Jie Wang (Tunnelling and Underground Space Technology, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Thermal degradation kinetics and behavior of MPN from Ginkgo biloba - Yu Kong; Yi-yuan Zhou; Ya-ping Wang; Xiao-fang Wang; Shan Duan; Mo-wen Su; Juan Zhao; Li-min Wang; Qing Kang; Xin-jun Du (Journal of Food Engineering, 2026)

Investigation on thermal runaway mechanism of tert-butyl peroxy benzoate using calorimetry analysis coupled with free radical spin-trapping technology - Zhi-Ping Li; Xiao-Yu Fang; Jun-Cheng Jiang; Lei Ni; Zhi-Quan Chen; Yuan-Yuan Wang (Journal of Environmental Chemical Engineering, 2026)

Upgrading oxygen vacancy and reducibility for enhancing synchronous abatement of Hg0 and toluene over Co-Mn-Ce trimetallic oxides fortified biochar catalysts - Jiaqing Li; Yanyan Feng; Lei Gao; Ping Fang; Yunqing Wang; Caiting Li; Jinke Xie; Yukai Quan; Siyou Li (Journal of Environmental Chemical Engineering, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

Efficient generation of highly reactive FeIVO2+ via the Fe(II)/Cl2 reaction for water purification - Shaoxiong He; Yuxin Wu; Wenlei Qin; Shenzhou Li; Wanting Cheng; Ping Li; Shizhong Wang; Gangfeng Ouyang; Mingshan Zhu; Jingyun Fang (Water Research, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

The overlooked role of nitrate in mediating electron transfer and enhancing reactive species generation in TiO2 photocatalytic water remediation - Zheng Hu; Jin Wu; Lingzhi Shen; Zili Lin; Zihong Xu; Zhenjun Xiao; Zheng Fang; Daguang Li; Ping Chen; Wenying Lv; Guoguang Liu (Process Safety and Environmental Protection, 2026)

Coupled effects of straw return practices on soil microbial functional potential and agricultural productivity in Semi-Arid Region - Rui-Zhi Liu; Xiao-Ya Zhao; Li-Jie Wang; Xing Zhang; Shu‑Ping Hu; Ju‑Lin Gao; Xiao‑Fang Yu; Qinggeer Borjigin (Plant and Soil, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

A novel polyphenol-metal chelation-based structure enabling epoxy with outstanding flame retardancy, toughening effect, smoke suppression performance and recyclability - Yao Deng; Hang-Ping Fang; Qing-Qing Bi; Ying-Ming Li; De-Yi Wang (Chemical Engineering Journal, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Allicin improves lipopolysaccharide-induced liver and intestinal damage in snakehead fish (Channa argus) through the NF-κB/Nrf2 signaling pathway: alleviation of inflammation, oxidative stress, and apoptosis - Ping Zhang; Wen Li; Zhiqiang Shen; Xinyu Zhang; Qiongya Fang; Siqi Jiao; Siyu An; Yidi Kong; Min Li; Guiqin Wang (Aquaculture International, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Enhancing free hydroxyl radical generation via noble metal-modified TiO₂ for efficient benzisothiazolinone degradation with reduced H₂O₂ consumption - Meng Xu; Xiao-qing Dong; Li-fang Chen; Ping Yu; Xin-yu Li; Shan-shan Lv; Ya-wen Qi; Wei Zhang; Peng Jiang; Xiao-long Zhou (Journal of Water Process Engineering, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Dual-dynamic polyimide and its thermally conductive adhesive featuring high glass transition temperature, recyclability, and strong adhesion - Fang Li; Ping Yu; Bin Wu; Ming Cao; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2026)

Role of eCIRP in Mediating Post-ischemia Microglial Phagocytosis via TREM-2 Receptor: Insights from Porcine and Mouse Cellular Models - Peijuan Li; Zhangping Sun; Yushu Chen; Zhen Fang; Dongping Yu; Ling Wang; Yanbo Ren; Ping Gong (Molecular Neurobiology, 2026)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Design of Ni-MOF@biochar heterostructures via ligand-induced distortion for highly selective N2H4 sensing - Bo Ran; Ping Hu; Jun Sun; Jialu Fang; Yan Li; Qihua Sun; Zhizhong Zhang; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

A high safety composite separator for powerful battery with ultra-long lifespan over 14,000 cycles at 10C - Ke Fang; Yan-yan Chen; Jian-wei Ji; Tian-kun Gao; Mei-qi Hu; Lian-li Zou; Ying Liu; Li-ping Zhou; Ming-quan Liu; Mao-xiang Jing (Chemical Engineering Journal, 2025)

Phosphorus incorporation drives charge distribution optimization and oxygen deficiency of cobalt‑nickel oxide nanoflakes with enhanced electrochemical performance for supercapacitor - Qinghai Ma; Ping Wang; Gaofeng Li; Fang Cui; Bin Yang; Zhijun Qiao; Dianbo Ruan; Xing Liu; Tieyu Cui (Chemical Engineering Journal, 2025)

Formation of coastal sand dunes along the northeastern South China Sea revealed by OSL chronology and its interaction with sea level change and human activity - Zibin Fang; Jiewen Xu; Gui Long; Ping Lai; Wen Wang; Ziyuan Wu; Yanwen Li; Wenwen Wu; Xinyi Luo; Yuexin Liu; Hua Tu; Guanjun Xu; et al. (CATENA, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Genome-wide analysis and functional validation of the GH1 gene family in cotton under salt stress - Liting Zhang; Junfeng Tang; Xiaoyu Tian; Hui Fang; Yifan Xu; Yiming Qian; Mengxue Jia; Ping Li; Baohua Wang; Zhimin Zhuang (Functional & Integrative Genomics, 2025)

CPT1A facilitated ferroptosis by forming feedback loop with Nrf2 via PI3K/AKT pathway in colorectal cancer - Xiao-huan Li; Feng Lv; Si-qi Li; Hao-wei Deng; Li-ping Tang; Ke-zhi Li; Li-ye Xie; Bang-li Hu; Shu-fang Ning (Apoptosis, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Surface modification of FeSi6.5 powders for additively manufactured catalysts with enhanced azo dye degradation - Xiang Zhang; Zhaoyang Li; Yingjie Song; Haishun Liu; Xiang Xiong; Meng Fang; Ping Zhang; Weiming Yang (Journal of Water Process Engineering, 2025)

Interactions between raw dark tea chemistry and dominant fungi shape Hei brick tea quality - Yating Guo; Haijing Cui; Xinxin Wang; Haowei Guo; Xinyu Feng; Anran Yan; Yani Pan; Lixin He; Liping Liu; Kexin Zhang; Hua Fang; Hesham R. El-Seedi; et al. (International Journal of Food Microbiology, 2025)

Development of novel smartphone-based micro-electrochemical immunosensors for the point of care testing and typing of Helicobacter pylori in serum and whole blood - Yuhan Wang; Ping Zhang; Wei Fang; Chuxian Zhou; Gengzhou Yang; Wenwei Huang; Lijie Zhang; Xiaoli Zhang; Bing Gu; Minmin Li; Jiajie Liang; Yong Tang (Chemical Engineering Journal, 2025)

Synergistic cation-anion interface engineering for uniform zinc deposition and stress mitigation in reinforced Zn metal anodes - Yixing Fang; Ping Li; Feng Sun; Chuyuan Lin; Xiao Yang; Zhen Wang; Guodong Miao; Lingxing Zeng; Yongchang Liu; Xuanhui Qu (Chemical Engineering Journal, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

The synergistic enhancement of adsorption for Pb2+ and organic dyes by a chitosan-based hydrogel as a multipollutant adsorbent - Yun Wang; Li-Ping Fang; Chen-Yang Li; Chang-Jing Cheng; Ting Liang; Xing-Bin Lv; Hai-Rong Yu (Journal of Environmental Chemical Engineering, 2025)

Biomass-derived organic aerogels endowed flexible polyurethane foam with excellent flame retardance, smoke suppression, bacteriostasis and enhanced mechanical property - Ying-Ming Li; Yao Deng; Hang-Ping Fang; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2025)

A rapid and ultrasensitive CRISPR/Cas12a-based assay for the accurate identification of T-even type phages - Chenhang Jiang; Yang Li; Ping Yu; Mengjun Fang; Di Huang; Xiangming Fang; Zhinan Xu (Biotechnology Letters, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Metabolic mechanism of a novel carboxylesterase YvaK in Priestia aryabhattai DPX-1 for carbamate insecticide indoxacarb detoxification - Ping Zou; Zijing Li; Shengyang Li; Yuehan Geng; Xin Ma; Xiangwei Wu; Rimao Hua; Liancheng Fang (Journal of Hazardous Materials, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

Structure and properties of esterified high-amylose corn starch combined with fatty acid prepared by enzymolysis and esterification reaction - Yali Ping; Hua Li; Fengyan Zhai; Zhenzhen Chen; Qingyuan Wang; Xiaoxue Fang (Food Chemistry, 2025)

Cell enlargement drives xylem hydraulic efficiency and safety in Pinus tabulaeformis on the Loess Plateau - Ping Ren; Jie Fang; Huiqin Song; Roberto Silvestro; Xiaoxia Li; Zongshan Li; Yafeng Wang; Sergio Rossi (Agricultural and Forest Meteorology, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Traditional and novel organophosphate esters in atmosphere of greenhouse covered with mulch films: Seasonal variations, partitioning and exposure risks - Fang Zhao; Sinuo Tian; Jing Liu; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Hua Ping; Cheng Li (Journal of Hazardous Materials, 2025)

Petrogenesis of rodingite in the Ngamring massif, Xigaze ophiolite (Southern Tibet): Implications for the evolution of the Neo-Tethys Ocean - Gui-Fang Ou; Zhong’ao Liu; Wen-Yong Duan; Guang-Ming Sun; Xu-Ping Li; Song-Jie Wang (Journal of Asian Earth Sciences, 2025)

Kaempferol improves recurrent spontaneous abortion outcomes and prevents oxidative stress damage by inhibiting the NF-kB signaling pathway - Guangli Xu; Huijuan Li; Lei Fang; Jingjing Guo; Chenyu Zhang; Jing Guo; Shuqing Ren; Ping Chen (Food and Chemical Toxicology, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Production regularity of exosomes and the characteristics of miRNA in exosomes from Eriobotrya Japonica L. suspension cells - Hui-hua Li; Mei-fang Wu; Qiu-ping Ye; Fei Chen; Wei Wang; Jian-yu Shi (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Arsenic mobilization by Bathyarchaeia in subsurface sediments at the Jianghan Plain, China - Zhou Jiang; Wenjie Fang; Yongguang Jiang; Yidan Hu; Yiran Dong; Ping Li; Liang Shi (Journal of Hazardous Materials, 2025)

Effects of pore structures of carbon paper on water management capability of a proton exchange membrane fuel cell - Yu-Ting Liu; Guo-Bao Huang; Xiao-Fang Zhang; Ting-Ting Yao; Li-Xia Cheng; Hong Zhu; Gang-Ping Wu (Fuel, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Mitigation mechanism of α-LA on AFB1-induced hepatocyte injury in snakehead fish (Channa argus): A potential substance - Min Li; Zhiqiang Shen; Ping Zhang; Sibo Peng; Xunan Li; Qiongya Fang; Xinyu Zhang; Ke Li; Siqi Jiao; Xiaorui Liu; Yidi Kong; Guiqin Wang (Aquaculture, 2025)

Anthropogenic nitrogen inputs favour increased nitrogen and organic carbon levels in Qinghai–Tibetan Plateau lakes: Evidence from sedimentary records - Ping Zhang; Xiangzhong Li; Fu-Jun Yue; Yuyan Zhang; Yuan Wang; Deyan Wu; Dongkun Liu; Fang Li; Xin Wang; Xuefang Ji (Water Research, 2025)

Study of the bubble flow evolution and load characteristics of a three-dimensional trimaran model entering water - Yanna Ping; Shuo Li; Fang Liu; Hang Xie (Ocean Engineering, 2025)

Livistona chinensis leaves bioorganic frame derived porous carbon material containing Fe-Nx active site as oxygen reduction electrocatalyst for zinc-air batteries - Kun Fang; Chen Ling; Yan-Fang Yao; Hao Zhang; Jia-Jie Wu; Li-Ping Si; Hai-Yang Liu (Journal of Environmental Chemical Engineering, 2025)

Lightweight deep learning model for embedded systems efficiently predicts oil and protein content in rapeseed - Mengshuai Guo; Huifang Ma; Xin Lv; Dan Wang; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Selective interfacial polymerization improves reversibility of Si anodes - Wen Yang; Shuwei Li; You Liu; Yanyan Li; Ping Jiang; Xiaobo Hong; Gaofeng Li; Bo Fan; Fang Chen; Liangdong Lin; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Construction and immunogenicity analysis of a recombinant baculovirus targeting the N protein of SARS-CoV-2 - Bohan Yu; Xiaoli Mo; Li Sui; Yujia Fang; Xudong Tang; Ping Qian (Biotechnology Letters, 2025)

Response to sea-level change in a non-deltaic coastal plain: Insights from cores chronologies - Yuexin Liu; Ziyuan Wu; Gui Long; Xinqi Feng; Ping Lai; Zibin Fang; Wenwen Wu; Jiewen Xu; Guanjun Xu; Hua Tu; Hongwei Li; Wen Wang; et al. (Geomorphology, 2025)

Gradient-Structured sodiophilic skeleton integrated with spatial confinement effect Enables high-rate and ultra-stable Na metal batteries - Fang-Yu Tao; Dan Xie; Wan-Yue Diao; Chang Liu; Godefroid Gahungu; Wen-Liang Li; Jing-Ping Zhang (Chemical Engineering Journal, 2025)

Multifunctional Sr/Zn-doped TiO2 micro/nanoporous coating enhances osseointegration by modulating signaling crosstalk of bone-related cells - Tian-Xia Zheng; Nuo-Ya Yang; Jiu-Peng Deng; Wei Dong; Li-Fang Feng; Yuanyuan-Ding; Jin-Ping Yang; Xin-Jia Cai; Yan Liu; Meng-Chun Qi (Chemical Engineering Journal, 2025)

Bimetallic MOF-derived Co/Ni@C and MXene co-decorated cellulose-derived carbon foams for absorption-dominated electromagnetic interference shielding - Fang Ren; Lin Ma; Chunjie Li; Tong Wu; Jiale Zhang; Lu Pei; Yanling Jin; Zhenfeng Sun; Zhengzheng Guo; Ping Song; Penggang Ren (Carbohydrate Polymers, 2025)

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

RsWRKY44 participated in anthocyanin biosynthesis regulation in radish through interaction with RsMYB1a - Biao Lai; Chenxi Gao; Li jiang; Li Wen; Xushuo Zhang; Wei Shen; Yanling Yu; Hanbing Yang; Fabo Chen; Ping Fang; Lina Du (Plant Cell Reports, 2025)

Raman spectroscopy coupled with chemometrics for identification of adulteration and fraud in muscle foods: a review - Haiyang Ma; Jiajun Guo; Guishan Liu; Delang Xie; Bingbing Zhang; Xiaojun Li; Qian Zhang; Qingqing Cao; Xiaoxue Li; Fang Ma; Yang Li; Guoling Wan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Developing the sensing mechanism of high-performance N2H4 sensors derived from waste cotton stalk using a one-step process - Ping Hu; Jun Sun; Bo Ran; Jialin Li; Jialu Fang; Qihua Sun; Ning Tian; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Genomic analysis of Vreelandella sp. F11 reveals its role in alginate utilization - Xin-Xiao Qu; Yu-Qi Zhang; Fei-Yu He; Xi-Ying Zhang; Peng Wang; Fei Xu; Yu-Qiang Zhang; Long-Sheng Zhao; Ping-Yi Li; Fang Zhao (Marine Genomics, 2025)

Liubao insect tea polyphenols ameliorate DSS-induced experimental colitis by protecting intestinal barrier and regulating intestinal microbiota - Xinyu Feng; Yanwen Chen; Lina Luo; Zhoutao Fang; Shicheng Ma; Zhongxia Li; Jing Huang; Yani Pan; Helin Lv; Shuying Gong; Xiaodong Zheng; Fangyuan Fan; et al. (Food Chemistry, 2025)

Impact of eight extruded starchy whole grains on glycemic regulation and fecal microbiota modulation - Fang Fang; Yu-Xin He; Hao-Qiang Wang; Yan-Li Zhang; Ya-dong Zhong; Xiao-Tian Hu; Shao-Ping Nie; Ming-Yong Xie; Jie-Lun Hu (Food Hydrocolloids, 2025)

An OLIF Cage Integrated with a Low-Profile Plate and Cross Screws Could Reduce the Risk of Postoperative Complications Biomechanically - Ping Cai; Chen Xu; Zifan Zhang; Zhongxin Fang; Chao Deng; Gang Chen; Guoyou Wang; Jingchi Li (Annals of Biomedical Engineering, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Cadmium translocation combined with metabolomics analysis revealed potential mechanisms of MT@MSN-CS and GSH@MSN-CS in reducing cadmium accumulation in rice (Oryza sativa L.) grains - Wen-Ze Fang; Jun-Qiao Chen; Jing-Dong Mao; Bao-Feng Zhang; Li-Ping Lou; Qi Lin (Environmental Science and Pollution Research, 2025)

High glucose induces renal tubular epithelial cell senescence by inhibiting autophagic flux - Ying Zhang; Yu Zhao; Yu-Qiu Liu; Ya-Ping Fang; Li Sun; Shan-Zhai Wei; Xiao-Dong Zhu; Xiao-Liang Zhang (Human Cell, 2025)

NAGK regulates the onset of puberty in female mice - Wei Zhang; Ping Qin; Mengxian Li; Zhihao Pan; Zhuoya Wu; Yanyun Zhu; Ya Liu; Yunsheng Li; Fugui Fang (Theriogenology, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Structural characterization and proteomic profiling of oviposition secretions across three rice planthopper species - Jia-Bao Lu; Peng-Peng Ren; Ying Tian; Yan-Yan Yang; Qing-Kai Feng; Xiao-Ya Zhang; Fang He; Hai-Jian Huang; Jian-Ping Chen; Jun-Min Li; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

Comprehensive physicochemical indicators analysis and quality evaluation model construction for the post-harvest ripening rapeseeds - Qiuhui Xu; Jie Wang; Dan Wang; Xin Lv; Li Fu; Ping He; Desheng Mei; Hong Chen; Fang Wei (Food Chemistry, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Fore-arc metasomatism by hybrid slab fluids during subduction initiation: Sr–Mg–Ca isotopes of rodingite, western Yarlung Zangbo suture zone - Gui-Fang Ou; Song-Jie Wang; Hao Deng; Wen-Yong Duan; Xu-Ping Li; Hans-Peter Schertl (Chemical Geology, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

ent-Kaurane diterpenoids from Isodon henryi and their anti-inflammatory activities - Yi-xiao Li; Jun Chi; Ling-xia Zhang; Fang Wang; Wei-jin Zhang; Zhi-min Wang; Li-ping Dai (Phytochemistry, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Study of Cerchar abrasive parameters of monomineralic rocks and its application for evaluating cutting efficiency - Xin-Fang Li; Xiao-Ping Zhang; Shao-Hui Tang; Wei-Qiang Xie; Xin-Mei Yang; Quan-Sheng Liu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

Holocene aeolian environmental dynamics in fixed and semi-fixed deserts over the arid Central Asia revealed by comprehensive sand-dune records - Min Cao; Ping Lü; Fang Ma; Linhai Yang; Junlin Yu; Zishu Xia; Chao Li (CATENA, 2024)

Assessment of Microseismic Events via Moment Tensor Inversion and Stress Evolution to Understand the Rupture of a Hard–Thick Rock Stratum - Jie-Fang Song; Cai-Ping Lu; Arno Zang; Xiu-Feng Zhang; Jian Zhou; Zhao-Wei Zhan; Li-Ming Zhao (Rock Mechanics and Rock Engineering, 2024)

Inhibition of BCAT1 expression improves recurrent miscarriage by regulating cellular dysfunction and inflammation of trophoblasts - Guangli Xu; Chao Tian; Yanru Li; Lei Fang; Jing Wang; Zhuqing Jing; Simeng Li; Ping Chen (Cell and Tissue Research, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Sensitivity of cloud microphysics to aerosol is highly associated with cloud water content: Implications for indirect radiative forcing - Yuan Wang; Hailing Jia; Ping Zhang; Fang Fang; Jiayi Li; Lei Zhu; Yang Wang; Tianshu Wang; Jiming Li (Atmospheric Research, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

A citrullinated antigenic vaccine in treatment of autoimmune arthritis - Xu Jin; Tianya Dong; Qian Wang; Yang Xie; Xiangyu Fang; Chaonan Wei; Shuyan Liu; Xi Zheng; Ping Wang; Danxue Zhu; Lulu Cao; Suwei Dong; et al. (Science Bulletin, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Protective Effect of CXCR7 Against Hypoxia/Reoxygenation Injury in Renal Tubular Epithelial Cells - Ping Meng; Chunli Liu; Jingchun Li; Ping Fang; Liling Chen (Cell Biochemistry and Biophysics, 2024)
Acute kidney injury (AKI) is a multifactorial syndrome with complex pathophysiology and prognosis. Ischaemia‒reperfusion injury (IRI) is a major cause of induced AKI. The aim of this study was to investigate the effect of upregulated CXCR7 expression on renal tubular epithelial cell apoptosis induced by hypoxia/reoxygenation (H/R). HK-2 cells were divided into three groups: control group (pcDNA3.1), hypoxia/reoxygenation + pcDNA3.1 group (H/R+pcDNA3.1) and CXCR7 overexpression + hypoxia/reoxygenation group (H/R+ Flag-CXCR7). Protein levels of renal tubular epithelial cell injury-, apoptosis- and autophagy-related markers were assessed by qRT‒PCR, Western blotting, flow cytometry (FCM), immunofluorescence and transmission electron microscopy (TEM). In addition, HK-2 cells were treated with the autophagy inhibitor 3-MA and divided into 3 groups: control group, 3-MA + pcDNA3.1 group, and 3-MA + Flag-CXCR7 group. Changes in autophagy and apoptosis in renal tubule epithelial cells were assessed by Western blotting and FCM. Compared with those in the control group, the protein and mRNA expression levels of CXCR7 in HK-2 cells were significantly lower under H/R conditions. Under H/R conditions, CXCR7 overexpression in HK-2 cells significantly downregulated the expression of NGAL. Moreover, CXCR7 overexpression significantly decreased H/R-induced cleaved PARP-1 and cleaved Caspase 3 levels, increased the level of the antiapoptotic protein BCL-2 and the autophagy-related molecules ATG5 and LC3B II, and significantly inhibited the expression of P62. Autophagy flow and TEM also showed that CXCR7 significantly promoted autophagy. CXCR7 significantly alleviated the 3-MA-induced inhibition of autophagy and increase in apoptosis. Upregulated CXCR7 expression can inhibit renal tubular epithelial cell apoptosis and damage by regulating autophagy. In conclusion, CXCR7 is a promising target for the prevention and/or treatment of AKI.

Copper-ion-complexed palygorskite as a novel nanozyme with enhanced peroxidase-like activity for sensitive colorimetric sensing - Ping Chen; Hui Zhong; Xiao-rong Li; Tingting Zhang; Xiang Wang; Fang Hu; Yubo Yan; Jiaxing Xu; Meisheng Li (Applied Clay Science, 2024)

Multi-spectroscopic characterization of organic salt components in medicinal plant - Lingyu Han; Fang Ma; Ping He; Qun Zhou; Zhanping Li; Suqin Sun (Food Chemistry, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Cactus-inspired moisture harvesting for sustainable and efficient high salinity desalination - Can Ge; Xianzhang Wu; Jiugang Li; Keshuai Liu; Duo Xu; Chong Gao; Yingcun Liu; Ping Sun; Ze Chen; Jian Fang (Desalination, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Litoamentenes A–K, eleven undescribed cembranoids with cytotoxicity from the South China Sea soft coral Litophyton amentaceum - Yuan Zong; Jun-Jie Yang; Kai Li; Yan-Fang Pei; Hui-Yue Hou; Yue Zhang; Ci-Li Wang; Ping-Lin Li (Phytochemistry, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

Insights into nitrogen-doped BiOBr with oxygen vacancy and carbon quantum dots photocatalysts for the degradation of sulfonamide antibiotics: Actions to promote exciton dissociation and carrier migration - Zhenchao Li; Chenghui Wen; Daguang Li; Zheng Fang; Zili Lin; Dezhu Liu; Yishun Wang; Xiaoyu Zhang; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2024)

Establishment and characterization of a golden pompano (Trachinotus blochii) fin cell line for applications in marine fish pathogen immunology - Jin-Feng Tong; Lang Yu; Rui-Hai Gan; Li-Ping Shi; Shao-Yang Bu; Yue Gu; Xin Wen; Jun-Long Sun; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

Synergistic signal amplification of ultrathin nanowire-like PtCoFeRuMo high-entropy nanozyme and Z-scheme WO3/ZnIn2S4 heterostructure for split-typed photoelectrochemical aptasensing of myoglobin - Fan Xu; Ben-Fang Xu; Qing-Ying Ai; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Karyotype analysis of Chinese chive germplasms with different ploidy levels and their evolutionary relationships - Peng-Qiang Yao; Jian-Hua Chen; Pei-Fang Ma; Li-Hua Xie; Jiang Shi; Shi-Ping Cheng (Genetic Resources and Crop Evolution, 2024)

A new lanostane-type triterpenoid from the marine shellfish symbiotic fungus Ceriporia lacerata CD7-5 - Sheng-Tao Fang; Feng-Ping Miao; Xiu-Li Yin; Nai-Yun Ji (Natural Product Research, 2024)

Insights into growth stages and genotypes in airborne Pb accumulation in Oryza sativa L. grains: Utilizing isotope fingerprinting alongside a model study - Qi Lin; Ming-Jin Zhuang; Wei Dai; Jing Fang; Bao-Feng Zhang; Jing-Dong Mao; Li-Ping Lou (Chemosphere, 2024)

Occurrence, potential sources, and ecological risks of traditional and novel organophosphate esters in facility agriculture soils: A case study in Beijing, China - Fang Zhao; Hua Ping; Jing Liu; Tianyu Zhao; Yingjun Wang; Guanglu Cui; Xuejiao Ha; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

High efficiency removal of NO using waste calcium carbide slag by facile KOH modification - Fang Wang; Hui Li; Jiyun Gao; Na Geng; Enzhu Jiang; Futing Xia; Mingwu Xiang; Lijuan Jia; Ping Ning (Journal of Environmental Sciences, 2024)

Redirecting the electron flow to coordinate oxidation and reduction reactions for efficient photocatalytic H2O2 production - Qichao Chen; Cai Ning; Jiawen Fang; Boyu Ping; Guiyang Li; Lingqiao Kong; Jiayi Chen; ZhengMing Sun; Jinlan Wang; Qiushi Ruan; Xianghong Niu; Li Tao (Chemical Engineering Journal, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Experimental study on the influence mechanism of soil additives on scraper wear during EPB-TBM tunnelling in abrasive sandy ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Wei-Qiang Xie; Jian Wu; Hao-Jie Wang; Xin-Fang Li (Bulletin of Engineering Geology and the Environment, 2024)

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

A novel Zr-P-modified nanomagnetic herbal biochar immobilized Cd and Pb in water and soil and enhanced the relative abundance of metal-resistant bacteria: Biogeochemical and spectroscopic investigations to identify the governing factors and potential mechanisms - Yueru Fang; Ping Wang; Lan Zhang; Han Zhang; Ran Xiao; Yuan Luo; Kuok Ho Daniel Tang; Ronghua Li; Hamada Abdelrahman; Zengqiang Zhang; Jörg Rinklebe; Sang Soo Lee; et al. (Chemical Engineering Journal, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Correlation of Gut Microbiota with Children Obesity and Weight Loss - Li-Jun Peng; Yan-Ping Chen; Fang Qu; Yan Zhong; Zhi-Sheng Jiang (Indian Journal of Microbiology, 2024)

Expansion of YALIcloneHR toolkit for Yarrowia lipolytica combined with Golden Gate and CRISPR technology - Qi Shen; Fang Yan; Ya-Wen Li; Jian Wang; Jia Ji; Wen-Xin Yan; Dan-Chen He; Ping Song; Tian-Qiong Shi (Biotechnology Letters, 2024)

Whole-cell bioreporter application for rapid evaluation of hazardous metal bioavailability and toxicity in bioprocess - Xiaokai Zhang; Yi Zhu; Evrim Elçin; Lizhi He; Boling Li; Mengyuan Jiang; Xing Yang; Xiu-Ping Yan; Xu Zhao; Zhenyu Wang; Fang Wang; Sabry M. Shaheen; et al. (Journal of Hazardous Materials, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

Self-assembly construction of 1D carbon nitride nanotubes and cobalt-modified for superior photocatalytic degradation of sulfonamide antibiotics - Zifeng Lin; Zhongquan Wang; Zihong Xu; Zhenjun Xiao; Zheng Fang; Jin Luo; Ping Li; Ping Chen; Wenying Lv; Guoguang Liu (Chemosphere, 2023)

Plant flavonoids bioavailability in vivo and mechanisms of benefits on chronic kidney disease: a comprehensive review - Yang Lin; Jingyu Fang; Zhiyu Zhang; Mohamed A. Farag; Zhenhao Li; Ping Shao (Phytochemistry Reviews, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Dry and wet seasonal variations of the sediment fungal community composition in the semi-arid region of the Dali River, Northwest China - Xin Chen; Guoce Xu; Ping Xiong; Jianbo Peng; Kang Fang; Shun Wan; Bin Wang; Fengyou Gu; Jing Li; Haijing Xiong (Environmental Science and Pollution Research, 2023)

Cytotoxic phenyl polyketides from Hypericum curvisepalum N. Robson - Qiu-Ying He; Hong Zeng; Qiu-Lan Zhang; Guan-Fang Qin; He-Bin Wang; Li-Ping Teng; Zhong-Bo Zhou (Natural Product Research, 2023)

Fast perception of rock mass strength and integrity in TBM tunnelling using in-situ penetration test - Wei-Qiang Xie; Xiao-Ping Zhang; Shao-Hui Tang; Xiao-Li Liu; Xin-Fang Li; Qi Zhang; Fa-Yuan Yan; Chen Xu; Quan-Sheng Liu (Tunnelling and Underground Space Technology, 2023)

Treating waste with waste: Facile KHCO3-modified calcium carbide slag for simultaneous removal of NO and SO2 - Fang Wang; Hui Li; Jiyun Gao; Chenhui Liu; Lijuan Jia; Jiayu Feng; Ping Ning (Fuel, 2023)

Semi-artificial photosynthetic system based on TiO2/Chlorophyll composite and microalgae for N2 fixation - Xiaoqin Pan; Wei Li; Yueping Fang; Haoran Zhang; Yong Xiao; Maxim Molokeev; San Ping Jiang; Yingliang Liu; Bingfu Lei (Chemical Engineering Journal, 2023)

Enhanced degradation of bisphenol S in water using a combination process of electrochemical oxidation with periodate activation - Pengjia Sun; Ping Sun; Yingsen Fang; Hui Liu; Bitao Xiong; Hui Wang; Xingao Li (Journal of Water Process Engineering, 2023)

Polystyrene microplastic attenuated the toxic effects of florfenicol on rice (Oryza sativa L.) seedlings in hydroponics: From the perspective of oxidative response, phototoxicity and molecular metabolism - Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Siyi Zhang; Zhiheng Li; Zhiguo Fang; Yuezhong Wen; Huijun Liu (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

A neglected contributor of thermal hydrolysis to sludge anaerobic digestion: Fulvic acids release and their influences - Mingze Shi; Hongbo Liu; Xuedong Zhang; Yajie Li; Fang Huang; Cheng Zhao; Jun Guo; Ping Wu; He Liu (Journal of Environmental Management, 2023)

Land-Use Change and Driving Force Analysis of Wetland in Poyang Lake Based on Remote Sensing - Zhili Xu; Bin Dong; Xiang Gao; Ping Wang; Chunqiu Ren; Sheng Li; Haifeng Xu; Fang Lei; Zezhu Wei; Zhipeng Lu; Xiao Liu (Journal of the Indian Society of Remote Sensing, 2023)

Knockdown of lncRNA Meg3 delays the onset of puberty in female rats - Hailing Li; Chunhuan Ren; Juntai Lu; Shuangshuang Xu; Xinbao Gong; Wei Zhang; Xu Yan; Jing Ye; Ping Qin; Ya Liu; Yunsheng Li; Yunhai Zhang; et al. (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effects of insulin-like growth factor 1, leukemia inhibitory factor, and basic fibroblast growth factor on goat oocyte maturation and early embryonic development in vitro - Zhao Gao-Ping; Shi Pei-Xin; Chang Qing; Wang Zi-Xin; Li Yun-Xia; Zhao Li-Xia; Sun Wei; Wu Meng; Bao Si-Qin; Cao Gui-Fang; Li Xi-He (Small Ruminant Research, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Hierarchical microsphere Flower-like SnIn4S8 with active sulfur sites for adsorption and removal of mercury from coal-fired flue gas - Yuanqin Xue; Xu Fang; Haoyu Jiang; Jiang Wu; Hailong Liu; Xin Li; Ping He; Fangqin Li; Yongfeng Qi; Qihang Gao; Yilin Fan (Chemical Engineering Journal, 2023)

Study of polycyclic aromatic hydrocarbons accumulation in bioretention facilities and its influence on microbial community structure - Ya-jiao Li; Yan-ting Shi; Ling-zhi Zhao; Ya-fang Li; Jia-ping Wang; Jia-ke Li (Environmental Science and Pollution Research, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Enhanced photochemical degradation and transformation of ciprofloxacin in a UV/calcium peroxide system: pH effects, defluorination kinetics, and different components numerical analysis - Zheng Fang; Zifeng Lin; Ping Chen; Mengying Feng; Haijin Liu; Zhenjun Xiao; Zili Lin; Dagaung Li; Dezhu Liu; Yudan Zhang; Wenying Lv; Guoguang Liu (Journal of Cleaner Production, 2023)

Environmental melamine exposure and adverse kidney outcomes in patients with type 2 diabetes mellitus - Yi-Chun Tsai; Chia-Fang Wu; Wei-Wen Hung; Ping-Shaou Yu; Chia-Chu Liu; Tusty-Jiuan Hsieh; Chu-Chih Chen; Sih-Syuan Li; Jia-Jen Chen; Yi-Wen Chiu; Shang-Jyh Hwang; Ming-Tsang Wu (Environmental Pollution, 2023)

Effects and mechanisms of natural products on Alzheimer’s disease - Zhijun Yang; Dan-Dan Zhou; Si-Yu Huang; Ai-Ping Fang; Hua-Bin Li; Hui-Lian Zhu (Critical Reviews in Food Science and Nutrition, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Baicalein sensitizes triple negative breast cancer MDA-MB-231 cells to doxorubicin via autophagy-mediated down-regulation of CDK1 - Fang Hua; Yi-Yi Xiao; Xin-Hui Qu; Shan-Shan Li; Kun Zhang; Chao Zhou; Jian-Le He; Ye Zhu; Yu-Ying Wan; Li-Ping Jiang; Fang-Fang Tou; Xiao-Jian Han (Molecular and Cellular Biochemistry, 2023)

Novel biphasic mechanism of the canonical Wnt signalling component PYGO2 promotes cardiomyocyte differentiation from hUC-MSCs - Yan Shi; Bin Qin; Xiongwei Fan; Yongqing Li; Yuequn Wang; Wuzhou Yuan; Zhigang Jiang; Ping Zhu; Jimei Chen; Yu Chen; Fang Li; Yongqi Wan; et al. (Cell and Tissue Research, 2023)
Human umbilical cord–derived mesenchymal stem cells (hUC-MSCs) are used to regenerate the myocardium during cardiac repair after myocardial infarction. However, the regulatory mechanism underlying their ability to form mesodermal cells and differentiate into cardiomyocytes remains unclear. Here, we established a human-derived MSCs line isolated from healthy umbilical cords and established a cell model of the natural state to examine the differentiation of hUC-MSCs into cardiomyocytes. Quantitative RT-PCR, western blotting, immunofluorescence, flow cytometry, RNA Seq, and inhibitors of canonical Wnt signalling were used to detect the germ-layer markers T and MIXL1 ; the markers of cardiac progenitor cells MESP1 , GATA4 , and NKX2.5 and the cardiomyocyte-marker cTnT to identify the molecular mechanism associated with PYGO2, a key component of the canonical Wnt signalling pathway that regulates the formation of cardiomyocyte-like cells. We demonstrated that PYGO2 promotes the formation of mesodermal-like cells and their differentiation into cardiomyocytes through the hUC-MSC-dependent canonical Wnt signalling by promoting the early-stage entry of β-catenin into the nucleus. Surprisingly, PYGO2 did not alter the expression of the canonical-Wnt, NOTCH, or BMP signalling pathways during the middle–late stages. In contrast, PI3K-Akt signalling promoted hUC-MSCs formation and their differentiation into cardiomyocyte-like cells. To the best of our knowledge, this is the first study to demonstrate that PYGO2 uses a biphasic mechanism to promote cardiomyocyte formation from hUC-MSCs.

Real-time perception of rock–machine interaction information in TBM tunnelling using muck image analysis - Wei-Qiang Xie; Xiao-Ping Zhang; Xiao-Li Liu; Chen-Yu Xu; Xin-Fang Li; Dan-Qing Song; Qing Ma; Nan Hu (Tunnelling and Underground Space Technology, 2023)

SOV sensitizes gastric cancer cells to radiation by suppressing radiation-induced autophagy in vitro and in vivo - Wen Wang; Xiao-gan Jiang; Ya-ping Bai; Heng Li; Ling-xi Gao; Teng Zhang; Fang-yi Dong; Wen-ping Ding; Yan Zhang (Tissue and Cell, 2023)

Transcriptomic and physiological analysis of the effect of octanoic acid on Meloidogyne incognita - Jian-Yu Wang; Qiu-Yue Li; Li Ren; Cheng Guo; Jian-Ping Qu; Zheng Gao; Hui-Fang Wang; Qian Zhang; Bo Zhou (Pesticide Biochemistry and Physiology, 2023)

Highly sensitive detection of thiram residues on fruit peel surfaces using a filter paper-based SERS sensor with AgNWs@ZIF-8 - Nuan Xu; Zhenhua Tang; Yan-Ping Jiang; Junlin Fang; Li Zhang; Xiaofang Lai; Qi-Jun Sun; Jing-Min Fan; Xin-Gui Tang; Qiu-Xiang Liu; Ji-Kang Jian (Journal of Environmental Chemical Engineering, 2023)

An integrated strategy combining network toxicology and feature-based molecular networking for exploring hepatotoxic constituents and mechanism of Epimedii Folium-induced hepatotoxicity in vitro - Zhen Zhao; Jin-Fa Du; Qiao-Lei Wang; Fang-Ning Qiu; Xu-Yan Chen; Feng-Jie Liu; Ping Li; Yan Jiang; Hui-Jun Li (Food and Chemical Toxicology, 2023)

Simultaneously achieving enhanced water adsorption and rapid adsorbed hydroxyl transfer toward MXene-based materials for highly efficient alkaline electrocatalytic hydrogen evolution - Yang Meng; Ping Zeng; Xiao-Yu Yang; Zhan Liu; Xiao-Yun Li; Cui-Fang Ye; Yu Li; Jin-Ping Liu; Bao-Lian Su; Li-Hua Chen; Yi-Long Wang (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

An endogenous neuropeptide hormone assists cancer cells in escaping from immune surveillance - Chang-Yu Yan; Yan-Ping Wu; Yi-Fang Li; Rong-Rong He (Science China Life Sciences, 2023)

Mining genes related to anthocyanin synthesis and regulation in different potato varieties based on comparative transcriptomics - En-fang Qi; Xiao-xia Jia; He-ping Lv; Wei Huang; Guo-hong Wen; Zhang Li; Jian-wu Li (Journal of Plant Biochemistry and Biotechnology, 2023)

Carp stocking and climate change are potentially more important factors than nutrient enrichment driving water quality deterioration in subtropical freshwater lakes in China - Haojie Su; Jianfeng Chen; Yun Li; Qingyang Rao; Congqiang Luo; Xuwei Deng; Hong Shen; Renhui Li; Jun Chen; Yuanfeng Sun; Jiamin Pan; Suhui Ma; et al. (Limnology and Oceanography, 2023)
Freshwater lakes across the world have undergone dramatic changes in biological components and water quality over the past several decades. Previous studies focused on potential drivers mainly on nutrient enrichment in the catchment. However, the relative importance of climate change and the top‐down cascade effects of fish stocking on water quality is not fully understood. Here, by compiling 155 lakes data with four periods of field investigation in subtropical lakes in China, we found no significant changes in water total nitrogen and total phosphorus in the past two decades. However, the phytoplankton abundance increased significantly, and the water clarity declined by 44.1%. We further found that carp stocking and climate change are potentially more important than nutrients driving water quality change, which is also evidenced in two lakes (Lake Donghu and Qiandao) with long‐term monitoring histories. Specifically, carp stocking can decrease the water clarity directly by stirring up sediment and indirectly by trophic cascade along the food web. For climatic factors, mean annual temperature (MAT) has a positive effect on phytoplankton abundance, while mean annual precipitation has a negative one, with climates overall having little effect on water clarity. In addition, nutrient enrichment and climate change also have strong interactions with carp stocking, which may enhance the top‐down effects on water quality. Our findings highlight that either MAT or carp stocking may become an overwhelming driver of water clarity decline, which provides new insights into the conservation strategy for water quality management in the subtropical lakes in China.

Neurotransmitter disturbances caused by methylmercury exposure: Microbiota-gut-brain interaction - Wenjuan Wang; Fang Chen; Li Zhang; Fuli Wen; Qing Yu; Ping Li; Aihua Zhang (Science of The Total Environment, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Myrochromanol analogues and trichothecene derivatives from the shellfish-derived fungus Albifimbria verrucaria - Sheng-Tao Fang; Yin-Ping Song; Feng-Ping Miao; Xiu-Li Yin; Nai-Yun Ji (Phytochemistry, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Novel function of a putative TaCOBL ortholog associated with cold response - Fang-Fang Liu; Ying-Xiu Wan; Wen-Xin Cao; Qi-Qi Zhang; Yao Li; Yan Li; Ping-Zhi Zhang; Hong-Qi Si (Molecular Biology Reports, 2023)

Melatonin inhibits senescence-associated melanin pigmentation through the p53-TYR pathway in human primary melanocytes and the skin of C57BL/6 J mice after UVB irradiation - Li-Ping Ma; Meng-Meng Liu; Fang Liu; Bo Sun; Si-Nian Wang; Jie Chen; Hui-Jie Yu; Juan Yan; Mei Tian; Ling Gao; Qing-Jie Liu (Journal of Molecular Medicine, 2023)
UVB exposure accelerates skin aging and pigmentation. Melatonin effectively regulates tyrosinase (TYR) activity and aging. The purpose of this study was to determine the association between premature senescence and pigmentation, and the mechanism of melanin synthesis effected by melatonin. Primary melanocytes were extracted and identified from the male foreskin. To inhibit TYR expression, primary melanocytes were transduced with the lentivirus pLKD-CMV-EGFP-2A-Puro-U6-TYR. The wild-type TYR ( + / + ) and TYR (–/–) or TYR ( + /–) knockout C57BL/6 J mice were used to determine the role of TYR on melanin synthesis in vivo. Results showed that UVB-induced melanin synthesis is dependent on TYR in primary melanocytes and mice. Furthermore, in primary melanocytes pretreated with Nutlin-3 or PFT-α to up or downregulate p53, results showed that premature senescence and melanin synthesis increased in primary melanocytes after UVB irradiation at 80 mJ/cm 2 , and further increased after being treated with Nutlin-3, while significantly decreased with PFT-α. In addition, melatonin inhibited UVB-induced premature senescence associated with inactivation of p53 and phosphorylation of p53 on Ser15 (ser-15), a decrease of melanin synthesis accompanied by reduced TYR expression. Moreover, skin erythema and pigmentation induced by UVB were reduced in the dorsal and ear skin of mice topically pretreated with 2.5% melatonin. These indicate that melatonin inhibits UVB-induced senescence-associated pigmentation via the p53-TYR pathway in primary melanocytes and prevents pigmentation obviously in the dorsal and ear skin of C57BL/6 J mice after UVB irradiation. Key messages P53 links UVB irradiation-induced senescence and senescence-associated pigmentation and regulates TYR in primary melanocytes after UVB irradiation. Melatonin inhibits senescence-associated pigmentation through the p53-TYR pathway in primary melanocytes. Melatonin prevents skin erythema and melanin pigmentation induced by UVB irradiation in the dorsal and ear skin of C57BL/6J mice.

In-situ Ni-oxidation-assisted coupling reduction of NiO and CO2 to synthesize core-shell Ni@octahedral carbon with energy storage properties - Ao Yu; Yinan Zhao; Longtao Zhu; Wenhao Yang; Ping Peng; Fang-Fang Li (Chemical Engineering Journal, 2023)

Single-cell HER2 quantification via instant signal amplification in microdroplets - Xiaoxian Liu; Yifan Zhu; Caoxin Li; Yanyun Fang; Jinna Chen; Fei Xu; Yanqing Lu; Perry Ping Shum; Ying Liu; Guanghui Wang (Analytica Chimica Acta, 2023)

Study on non-point source pollution characteristics under different spatial scales: a case study of Hanjiang River Basin, China - Ya-jiao Li; Jia-ping Wang; Zi-hang Zhang; Gai-rui Hao; Ya-fang Li; Jia-ke Li (Environmental Science and Pollution Research, 2023)

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

ARHGEF15 is expressed in undifferentiated spermatogonia but is not required for spermatogenesis in mice - Yu-Jun Wang; Shuang Li; Hai-Ping Tao; Xiao-Na Zhang; You-Gui Fang; Qi-En Yang (Reproductive Biology, 2023)

Sonocatalytic degradation of tetracycline by BiOBr/FeWO4 nanomaterials and enhancement of sonocatalytic effect - Liang Xu; Xue-Qian Wu; Chun-Yu Li; Ni-Ping Liu; Hui-Li An; Wan-Ting Ju; Wen Lu; Bin Liu; Xiao-Fang Wang; Yang Wang; Xin Wang (Journal of Cleaner Production, 2023)

Ammonia-oxidizing archaea and comammox Nitrospira clade B as freeze–thaw resistant nitrifiers in wetland soils - Xiufeng Tang; Jun Li; Dongyao Sun; Linfa Fang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2023)

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Stable isotope and elemental profiles determine geographical origin of saffron from China and Iran - Jing Nie; Jian Yang; Cuiling Liu; Chunlin Li; Shengzhi Shao; Chunxia Yao; Bilian Chen; Yi Tao; Fang Wang; Yongzhi Zhang; Karyne M. Rogers; Ping Wang; et al. (Food Chemistry, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Initial water rights allocation of Industry in the Yellow River basin driven by high-quality development - Xiang-nan Chen; Fang Li; Feng-ping Wu; Xia Xu; Yue Zhao (Ecological Modelling, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

Nightside 135.6 nm emission enhancements of mid/low latitudes during geomagnetic storms as observed by the ionosphere PhotoMeter (IPM) on the Chinese meteorological satellite FY-3D - Fang Jiang; Tian Mao; XiaoXin Zhang; Li-Ping Fu (Advances in Space Research, 2023)

Resource utilization of hazardous solid waste blast furnace dust: Efficient wet desulfurization and metal recovery - Xuejin Yang; Binghua Xie; Fang Wang; Ping Ning; Kai Li; Lijuan Jia; Jiayu Feng; Futing Xia (Chemosphere, 2023)

Dual seasonal pattern for hemorrhagic fever with renal syndrome and its potential determinants in China - Chen-Long Lv; Yao Tian; Yan Qiu; Qiang Xu; Jin-Jin Chen; Bao-Gui Jiang; Zhong-Jie Li; Li-Ping Wang; Simon I. Hay; Wei Liu; Li-Qun Fang (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Metabolomics and proteomics reveal the toxicological mechanisms of florfenicol stress on wheat (Triticum aestivum L.) seedlings - Hanmei Chen; Jiaojun Jin; Shuhao Hu; Luoqin Shen; Ping Zhang; Zhiheng Li; Zhiguo Fang; Huijun Liu (Journal of Hazardous Materials, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

Preparation of XCu@TiO2 adsorbent for high-efficient PH3 removal in anaerobic environment and evaluation of desulfurization activity of deactivated adsorbent - Lijuan Jia; Xuejin Yang; Kaiqiang Hu; Jiayu Feng; Fang Wang; Kai Li; Xin Sun; Fei Wang; Ping Ning (Chemical Engineering Journal, 2023)

Effective immobilization of Cd(II) in soil by biotic zero-valent iron and coexisting sulfate - Weiquan Li; Yuhang Yang; Xueying Lin; Weizhao Yin; Zhanqiang Fang; Ping Li; Jinhua Wu (Chemosphere, 2023)

Characteristics and origin of Lower Triassic Feixianguan Formation dolostones on the west side of Kaijiang–Liangping Trough, northeastern Sichuan Basin, China - Ling Zhou; Guangwei Wang; Ya Zhang; Yanping Qiao; Fang Hao; Rui Xu; Li Quan; Ping Wang (Marine and Petroleum Geology, 2023)

Enhanced Cd(II) immobilization in sediment with zero-valent iron induced by hydrogenotrophic denitrification - Ying Chen; Weiquan Li; Huaitian Bu; Weizhao Yin; Ping Li; Zhanqiang Fang; Jinhua Wu (Journal of Hazardous Materials, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Temperature tolerant all-solid-state touch panel with high stretchablity, transparency and self-healing ability - Zhenglin Chen; Fang Li; Likun Zhang; Zhengyang Lei; Canhui Yang; Chufan Xiao; Lijin Lian; Xi Yuan; Gul Ijaz; Jia'e Yang; Zijun Lin; Yunfeng He; et al. (Chemical Engineering Journal, 2023)

Insights into CQDs-doped perylene diimide photocatalysts for the degradation of naproxen - Zheng Fang; Yang Liu; Ping Chen; Daguang Li; Haijin Liu; Zhenjun Xiao; Yixun Zheng; Zifeng Lin; Jin Luo; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2023)

Key technology for the construction and inspection of long-distance underwater tunnel for 1000 kV gas-insulated transmission line - Xiao-Ping Zhang; Shao-Hui Tang; Quan-Sheng Liu; Hao-Jie Wang; Xin-Fang Li; Peng Chen; Hao Liu (Bulletin of Engineering Geology and the Environment, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

MdbHLH51 plays a positive role in anthocyanin accumulation in ‘Red Delicious’ apples - Gai-Xing Ning; Wen-Fang Li; Ming-Yu Chu; Zong-Huan Ma; Ping Wang; Juan Mao; Bai-Hong Chen (Trees, 2022)

Energy substrate metabolism and oxidative stress in metabolic cardiomyopathy - Ze Chen; Zhao-Xia Jin; Jingjing Cai; Ruyan Li; Ke-Qiong Deng; Yan-Xiao Ji; Fang Lei; Huo-Ping Li; Zhibing Lu; Hongliang Li (Journal of Molecular Medicine, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

Overexpression of PYGO1 promotes early cardiac lineage development in human umbilical cord mesenchymal stromal/stem cells by activating the Wnt/β-catenin pathway - Jie Shen; Xiushan Wu; Ping Zhu; Jian Zhuang; Bin Qin; Fang Sun; Wuzhou Yuan; Xiongwei Fan; Zhigang Jiang; Fang Li; Yongqing Li; Yuequn Wang; et al. (Human Cell, 2022)

Bio-organic Fertilizer with Bacillus subtilis F2 Promotes Strawberry Plant Growth and Changes Rhizosphere Microbial Community - Li Liu; Xiang Li; Tianyu Li; Yuan Xie; Zhuoyang Cao; Ping Fang (Journal of Soil Science and Plant Nutrition, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

The initial impoundment of the Baihetan reservoir region (China) exacerbated the deformation of the Wangjiashan landslide: characteristics and mechanism - Xiaoyu Yi; Wenkai Feng; Mingtang Wu; Zhiping Ye; Yunfeng Fang; Ping Wang; Renjiang Li; Jiawei Dun (Landslides, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Ginseng volatile oil prolongs the lifespan and healthspan of Caenorhabditis elegans - Lixin Wang; Ping Qiao; Zhuoer Ouyang; Danyang Li; Jingtong Zheng; Guoqiang Wang; Fang Wang (Biogerontology, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

CaMKIIα Signaling Is Required for the Neuroprotective Effects of Dl-3-n-Butylphthalide in Alzheimer’s Disease - Bing-qiu Li; Ling-zhi Xu; Fang-yu Li; Ying Li; Yu Zhao; Heng Zhang; Mei-na Quan; Jian-ping Jia (Molecular Neurobiology, 2022)

Components Analysis of Recycled Alkali Black Liquor Combined with Corn Straw Under Ozone Pretreatment - Xiaohong Lu; Fei Li; Yiming Li; Shuo Fang; Xia Zhou; Zhezhen Zhao; Ping Liu (BioEnergy Research, 2022)

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Synthesis and anticancer activity of Boc-Gly-Pro dipeptide-annonaceous acetogenin prodrugs targeting fibroblast activation protein or other hydrolytic enzymes - Jing-Fang Shi; Ping Wu; Han-Xiang Li; Xiao-Yi Wei; Zi-Hua Jiang (Medicinal Chemistry Research, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

A Data-Intensive Numerical Modeling Method for Large-Scale Rock Strata and Its Application in Mining Subsidence Prediction - Ya-Qiang Gong; Guang-Li Guo; Li-Ping Wang; Huai-Zhan Li; Guang-Xue Zhang; Zhen Fang (Rock Mechanics and Rock Engineering, 2022)

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

Oxidation of organoarsenicals and antimonite by a novel flavin monooxygenase widely present in soil bacteria - Jun Zhang; Jian Chen; Yi‐Fei Wu; Zi‐Ping Wang; Ji‐Guo Qiu; Xiao‐Long Li; Feng Cai; Ke‐Qing Xiao; Xiao‐Xu Sun; Barry P. Rosen; Fang‐Jie Zhao (Environmental Microbiology, 2022)
Summary Arsenic can be biomethylated to form a variety of organic arsenicals differing in toxicity and environmental mobility. Trivalent methylarsenite (MAs(III)) produced in the methylation process is more toxic than inorganic arsenite (As(III)). MAs(III) also serves as a primitive antibiotic and, consequently, some environmental microorganisms have evolved mechanisms to detoxify MAs(III). However, the mechanisms of MAs(III) detoxification are not well understood. In this study, we identified an arsenic resistance ( ars ) operon consisting of three genes, arsRVK , that contribute to MAs(III) resistance in Ensifer adhaerens ST2. ArsV is annotated as an NADPH‐dependent flavin monooxygenase with unknown function. Expression of arsV in the arsenic hypersensitive Escherichia coli strain AW3110 Δars conferred resistance to MAs(III) and the ability to oxidize MAs(III) to MAs(V). In the presence of NADPH and either FAD or FMN, purified ArsV protein was able to oxidize both MAs(III) to MAs(V) and Sb(III) to Sb(V). Genes with arsV ‐like sequences are widely present in soils and environmental bacteria. Metagenomic analysis of five paddy soils showed the abundance of arsV ‐like sequences of 0.12–0.25 ppm. These results demonstrate that ArsV is a novel enzyme for the detoxification of MAs(III) and Sb(III) and the genes encoding ArsV are widely present in soil bacteria.

Seasonal variations of rotifer communities in three climatic zones: effects of environmental parameters on changes of functional groups - Fang-Ping Qian; Xin-Li Wen; Yi-Long Xi (Limnology, 2022)

Performance and mechanisms of fly ash for graphene oxide removal from aqueous solution - Ping Jiang; Lin Zhou; Wei Wang; Na Li; Fang Zhang (Environmental Science and Pollution Research, 2022)

Colchicine-induced tetraploidy influences morphological and cytological characteristics and enhances accumulation of anthocyanins in a red-fleshed radish (Raphanus sativus L.) - Fabo Chen; Jian Gao; Wenbo Li; Yi Liu; Ping Fang; Zhihang Peng (Horticulture, Environment, and Biotechnology, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Nitrogen contaminants damage on intestinal epithelial tight junctions: a review - Guo-ping Zhao; Jin-wang Li; Fang-wei Yang; Xiao-yu Wang; Fa-zheng Ren; Guo-fang Pang; Yi-xuan Li (Environmental Chemistry Letters, 2021)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Design and Evaluation of a Novel Transversal Double-bud Sugarcane Planter with Seed Pre-cutting - Jia-Qin Zhong; Li-Min Tao; Shang-Ping Li; Fang-Lan Ma; Yuan-Ling Chen (Sugar Tech, 2021)

Responses of leaf litter decomposability to nitrogen and phosphorus additions are associated with cell wall carbohydrate composition in a subtropical plantation - Xiang-Min Fang; Xiu-Lan Zhang; Ying-Ying Zong; Wen-Qing Li; Jian-Jun Li; Li-Ping Guo; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Mapping-by-sequencing the locus of EMS-induced mutation responsible for tufted-fuzzless seed phenotype in cotton - Marina Naoumkina; Gregory N. Thyssen; David D. Fang; Efrem Bechere; Ping Li; Christopher B. Florane (Molecular Genetics and Genomics, 2021)

An experimental study on cutting tool hardness optimization for shield TBMs during dense fine silty sand ground tunneling - Xiao-Ping Zhang; Shao-Hui Tang; Quan-Sheng Liu; Xin-Bin Tu; Peng Chen; Fang-Yi Li (Bulletin of Engineering Geology and the Environment, 2021)

The sub-inhibitory concentration of cinnamaldehyde resists Aeromonas hydrophila pathogenicity via inhibition of W-pili production - Ping Ouyang; Jiehao Chen; Lizi Yin; Yi Geng; Defang Chen; Kaiyu Wang; Weiming Lai; Hongrui Guo; Jing Fang; Zhengli Chen; Li Tang; Chao Huang; et al. (Aquaculture International, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

HDAC3 Downregulation Improves Cerebral Ischemic Injury via Regulation of the SDC1-Dependent JAK1/STAT3 Signaling Pathway Through miR-19a Upregulation - Hua Fang; Hua-Feng Li; Ming-Hai He; Miao Yang; Jian-Ping Zhang (Molecular Neurobiology, 2021)

Integrative analysis of miRNAs and mRNAs revealed regulation of lipid metabolism in dairy cattle - Lixin Xia; Zhihui Zhao; Xianzhong Yu; Chunyan Lu; Ping Jiang; Haibin Yu; Xiaohui Li; Xiang Yu; Juan Liu; Xibi Fang; Runjun Yang (Functional & Integrative Genomics, 2021)

3D DEM analysis on tractive trafficability of a lunar rover wheel with bionic wheel lugs - Hao Pang; Rui Zhang; Ping Ge; Fang Liu; Chengjin Wang; Wenchao Dong; Tao Li; Jianqiao Li (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Synthesis and antitumor evaluation of (aryl)methyl-amine derivatives of dehydroabietic acid-based B ring-fused-thiazole as potential PI3K/AKT/mTOR signaling pathway inhibitors - Nai-Yuan Chen; Yu-Lan Xie; Guo-Dong Lu; Fang Ye; Xin-Yu Li; Yu-Wen Huang; Ming-Li Huang; Tie-Yu Chen; Cui-Ping Li (Molecular Diversity, 2021)

Fine mapping QTL and mining genes for protein content in soybean by the combination of linkage and association analysis - Xiyu Li; Ping Wang; Kaixin Zhang; Shulin Liu; Zhongying Qi; Yanlong Fang; Yue Wang; Xiaocui Tian; Jie Song; Jiajing Wang; Chang Yang; Xu Sun; et al. (Theoretical and Applied Genetics, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Thermaurantiacus tibetensis gen. nov., sp. nov., a novel moderately thermophilic bacterium isolated from hot spring microbial mat in Tibet - Yu-Zhen Ming; Lan Liu; Ai-Ping Lv; Wen-Dong Xian; Ze-Tao Liu; Meng-Meng Li; Jian-Yu Jiao; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Biopharmaceutics Applications of Physiologically Based Pharmacokinetic Absorption Modeling and Simulation in Regulatory Submissions to the U.S. Food and Drug Administration for New Drugs - Fang Wu; Heta Shah; Min Li; Peng Duan; Ping Zhao; Sandra Suarez; Kimberly Raines; Yang Zhao; Meng Wang; Ho-pi Lin; John Duan; Lawrence Yu; et al. (The AAPS Journal, 2021)

Groundwater sources, flow patterns, and hydrochemistry of the Central Yinchuan Plain, China - Ying Li; Ping Wu; Xiao-Qin Huang; Bo Zhang; Zhao-Xiang Xu; Yang Li; Jie Li; Lu-Chen Wang; Yu-Fang Sun; Xu-Chen Meng; Cheng-Wen Wang; Zi-Zhao Cai (Hydrogeology Journal, 2021)

Antimonate removal by diatomite modified with Fe-Mn oxides: application and mechanism study - Qiu-Yi Dong; Yu-Chun Fang; Bin Tan; Aura Ontiveros-Valencia; Ang Li; He-Ping Zhao (Environmental Science and Pollution Research, 2021)

Identification of Colletotrichum brevisporum causing fruit rot in yellow passion fruit (Passiflora edulis f. flavicarpa) in China - Fang Qiu; Xi Li; Chang Ping Xie; Jing Li; Fei Qing Zheng (Australasian Plant Pathology, 2021)

Elucidation of sequence polymorphism in fuzzless-seed cotton lines - Marina Naoumkina; Gregory N. Thyssen; David D. Fang; Ping Li; Christopher B. Florane (Molecular Genetics and Genomics, 2021)

Valine acts as a nutritional signal in brain to activate TORC1 and attenuate postprandial ammonia-N excretion in Chinese perch (Siniperca chuatsi) - Jie Wang; Xu-Fang Liang; Shan He; Yan-Peng Zhang; Jiao Li; Kang Huang; Lin-Jie Shi; Ping Ren (Fish Physiology and Biochemistry, 2020)

Possible effects of leaf tissue characteristics of oilseed rape Brassica napus on probing and feeding behaviors of cabbage aphids Brevicoryne brassicae - Zhong-Ping Hao; Hai-Xia Zhan; Ling-Ling Gao; Fang Huang; Li-Ni Zhu; Shu-Min Hou (Arthropod-Plant Interactions, 2020)

What factors determine the mass elevation effect of the Tibetan Plateau? - Fang Han; Li Wan; Hong-zhi Wu; Bai-ping Zhang; Lan Gao; Ge Song (Journal of Mountain Science, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Removal of SO2 and NOx from flue gas using mud-phosphorus slurry - Lijuan Jia; Zizhen Li; Qian Yu; Jiyun Gao; Chenhui Liu; Tiancheng Liu; Ping Ning; Fang Wang (Environmental Science and Pollution Research, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Enhancement methane fermentation of Enteromorpha prolifera waste by Saccharomyces cerevisiae: batch kinetic investigation, dissolved organic matter characterization, and synergistic mechanism - Shunan Zhao; Ping Li; Hongli Fang; Liuying Song; Dunjie Li; Rutao Liu; Qigui Niu (Environmental Science and Pollution Research, 2020)

PX Domain-Containing Kinesin KIF16B and Microtubule-Dependent Intracellular Movements - Bo-jie Li; Hao Chen; Su-su Jiang; Chu-yao Wang; Qin-hui Tuo; Shi-yin Long; Cai-ping Zhang; Duan-fang Liao (The Journal of Membrane Biology, 2020)

Outbreak of carp edema virus disease in cultured ornamental koi in a lower temperature in China - Ping Ouyang; Yaojia Zhou; Ruixue Yang; Zhuangzhi Yang; Kaiyu Wang; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Li Tang; et al. (Aquaculture International, 2020)

An EMS-induced mutation in a tetratricopeptide repeat-like superfamily protein gene (Ghir_A12G008870) on chromosome A12 is responsible for the liy short fiber phenotype in cotton - David D. Fang; Marina Naoumkina; Gregory N. Thyssen; Efrem Bechere; Ping Li; Christopher B. Florane (Theoretical and Applied Genetics, 2020)

Research on ecological risk assessment in land use model of Shengjin Lake in Anhui province, China - Liang Peng; Bin Dong; Ping Wang; Shuwei Sheng; Li Sun; Lei Fang; Haoran Li; Liping Liu (Environmental Geochemistry and Health, 2019)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

HprK Xcc is a serine kinase that regulates virulence in the Gram‐negative phytopathogen Xanthomonas campestris - Rui‐Fang Li; Ping Cui; Ping‐Zhen Wei; Xing‐Yan Liu; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2019)
Summary The HprK serine kinase is a component of the phosphoenolpyruvate phosphotransferase system (PTS) of bacteria that generally regulates catabolite repression through phosphorylation/dephosphorylation of the PTS protein PtsH at a conserved serine residue. However, many bacteria do not encode a complete PTS or even have an HprK homologue. Xanthomonas campestris pv. campestris ( Xcc ) is a pathogen that cause black rot disease in crucifer plants and one of the few Gram‐negative bacteria that encodes a homologue of HprK protein (herein HprK Xcc ). To gain insight into the role of HprK Xcc and other PTS‐related components in Xcc we individually mutated and phenotypically assessed the resulting strains. Deletion of hprK Xcc demonstrated its requirement for virulence and other diverse cellular processes associated including extracellular enzyme activity, extracellular‐polysaccharide production and cell motility. Global transcriptome analyses revealed the HprK Xcc had a broad regulatory role in Xcc . Additionally, through overexpression, double gene deletion and transcriptome analysis we demonstrated that hprK Xcc shares an epistatic relationship with ptsH . Furthermore, we demonstrate that HprK Xcc is a functional serine kinase, which has the ability to phosphorylate PtsH. Taken together, the data illustrates the previously unappreciated global regulatory role of HprK Xcc and previously uncharacterized PTS components that control virulence in this pathogen.

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Effects of AM fungi and grass endophytes on perennial ryegrass Bipolaris sorokiniana leaf spot disease under limited soil nutrients - Yane Guo; Ping Gao; Fang Li; Tingyu Duan (European Journal of Plant Pathology, 2019)

The Molecular Mechanisms of Protective Role of Se on the G0/G1 Phase Arrest Caused by AFB1 in Broiler’s Thymocytes - Ke Guan; Hang Li; Zhicai Zuo; Fengyuan Wang; Ping Hu; Xi Peng; Jing Fang; Hengmin Cui; Gang Shu; Ping Ouyang (Biological Trace Element Research, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

A novel variant of Gh_D02G0276 is required for root-knot nematode resistance on chromosome 14 (D02) in Upland cotton - Martin J. Wubben; Gregory N. Thyssen; Franklin E. Callahan; David D. Fang; Dewayne D. Deng; Jack C. McCarty; Ping Li; Md Sariful Islam; Johnie N. Jenkins (Theoretical and Applied Genetics, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Inhibition of thymocyte autophagy-associated CD4+T thymopoiesis is involved in asthma susceptibility in mice exposed to caffeine prenatally - Han-xiao Liu; Hui-yi Yan; Wen Qu; Xiao Wen; Li-fang Hou; Wen-hao Zhao; Jie Ping (Archives of Toxicology, 2019)

Whole genome sequencing of a MAGIC population identified genomic loci and candidate genes for major fiber quality traits in upland cotton (Gossypium hirsutum L.) - Gregory N. Thyssen; Johnie N. Jenkins; Jack C. McCarty; Linghe Zeng; B. Todd Campbell; Christopher D. Delhom; Md. Sariful Islam; Ping Li; Don C. Jones; Brian D. Condon; David D. Fang (Theoretical and Applied Genetics, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Quantifying the ecological stability of artificial aquatic ecosystems: a case study of an artificial lake in Chengdu, China - Fang-Fang Chen; Gong-Ping Su; Hai-Yan Mou; Xuan Liang; Yi Chen; Tian-Qi Ao; Wen-Qing Chen; Yun-Zhen Li (Aquatic Sciences, 2019)

Characterizing the Mass Elevation Effect across the Tibetan Plateau - Fang Han; Bai-ping Zhang; Fang Zhao; Li Wan; Jing Tan; Tian Liang (Journal of Mountain Science, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Effects of cadmium stress on the antioxidant system and chlorophyll fluorescence characteristics of two Taxodium clones - Ying-Li Ma; Hui-Fang Wang; Ping Wang; Chao-Guang Yu; Si-Qian Luo; Yu-Feng Zhang; Yin-Feng Xie (Plant Cell Reports, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

The Protective Role of Selenium in AFB1-Induced Tissue Damage and Cell Cycle Arrest in Chicken’s Bursa of Fabricius - Ping Hu; Zhicai Zuo; Fengyuan Wang; Xi Peng; Ke Guan; Hang Li; Jing Fang; Hengmin Cui; Gang Su; Ping Ouyang; Yi Zhou (Biological Trace Element Research, 2018)

Application of Phragmites australis to remove phenol from aqueous solutions by chemical activation in batch and fixed-bed columns - Sheng-Li Shi; Jun-Ping Lv; Qi Liu; Fang-Ru Nan; Xiao-Yan Jiao; Jia Feng; Shu-Lian Xie (Environmental Science and Pollution Research, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Depth treatment of coal-chemical engineering wastewater by a cost-effective sequential heterogeneous Fenton and biodegradation process - Yili Fang; Weizhao Yin; Yanbin Jiang; Hengjun Ge; Ping Li; Jinhua Wu (Environmental Science and Pollution Research, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

Potential high-frequency off-target mutagenesis induced by CRISPR/Cas9 in Arabidopsis and its prevention - Qiang Zhang; Hui-Li Xing; Zhi-Ping Wang; Hai-Yan Zhang; Fang Yang; Xue-Chen Wang; Qi-Jun Chen (Plant Molecular Biology, 2018)

Molecular characterization of a novel luteovirus infecting apple by next-generation sequencing - Pan Shen; Xin Tian; Song Zhang; Fang Ren; Ping Li; Yun-qi Yu; Ruhui Li; Changyong Zhou; Mengji Cao (Archives of Virology, 2018)

An arbuscular mycorrhizal fungus and Epichloë festucae var. lolii reduce Bipolaris sorokiniana disease incidence and improve perennial ryegrass growth - Fang Li; Yan’e Guo; Michael J. Christensen; Ping Gao; Yanzhong Li; Tingyu Duan (Mycorrhiza, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

C21 steroid derivatives from the Dai herbal medicine Dai-Bai-Jie, the dried roots of Marsdenia tenacissima, and their screening for anti-HIV activity - Xu Pang; Li-Ping Kang; Xiao-Mei Fang; He-Shui Yu; Li-Feng Han; Yang Zhao; Li-Xia Zhang; Li-Yan Yu; Bai-Ping Ma (Journal of Natural Medicines, 2018)

The V-ATPase subunit A is essential for salt tolerance through participating in vacuolar Na+ compartmentalization in Salicornia europaea - Sulian Lv; Ping Jiang; Fang Tai; Duoliya Wang; Juanjuan Feng; Pengxiang Fan; Hexigeduleng Bao; Yinxin Li (Planta, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Changes in Histopathology, Enzyme Activities, and the Expression of Relevant Genes in Zebrafish (Danio rerio) Following Long-Term Exposure to Environmental Levels of Thallium - Li-Ping Hou; Yang Yang; Hu Shu; Guang-Guo Ying; Jian-Liang Zhao; Yi-Bing Chen; Yong-Heng Chen; Gui-Zhen Fang; Xin Li; Ji-Sheng Liu (Bulletin of Environmental Contamination and Toxicology, 2017)

A potent indolylquinoline alleviates growth of human lung cancer cell tumorspheres - Yu-Ling Ni; Chang-Hung Hsieh; Seung-Hun Kim; Jing-Ping Wang; Chun-Li Su; Ching-Fa Yao; Kang Fang (Apoptosis, 2017)

Genome-wide analysis of GDSL-type esterases/lipases in Arabidopsis - Chia-Ping Lai; Li-Min Huang; Long-Fang O. Chen; Ming-Tsair Chan; Jei-Fu Shaw (Plant Molecular Biology, 2017)

Potential hypoglycaemic activity phenolic glycosides from Moringa oleifera seeds - Fang Wang; Huan-Huan Zhong; Wei-Ke Chen; Qing-Pu Liu; Cun-Yu Li; Yun-Feng Zheng; Guo-Ping Peng (Natural Product Research, 2017)

Establishment of a gene function analysis system for the euhalophyte Salicornia europaea L. - Fang Tai; Sulian Lv; Ping Jiang; Jinhui Wang; Juanjuan Feng; Yinxin Li (Plant Cell Reports, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Occurrence and genetic diversity analysis of apple stem pitting virus isolated from apples in China - Guo-Jun Hu; Ya-Feng Dong; Zun-Ping Zhang; Xu-Dong Fan; Fang Ren; Zhengnan Li (Archives of Virology, 2017)

Response of linear and cyclic electron flux to moderate high temperature and high light stress in tomato - Tao Lu; Jie-wei Shi; Zhou-ping Sun; Ming-fang Qi; Yu-feng Liu; Tian-lai Li (Journal of Zhejiang University-SCIENCE B, 2017)

Quantitative trait loci analysis for net ginning energy requirements in upland cotton (Gossypium hirsutum L.) - Efrem Bechere; David D. Fang; Hirut Kebede; Robert G. Hardin; Md. S. Islam; Ping Li; Jodi Scheffler (Euphytica, 2017)

Spontaneous Remission of Subcutaneous Scedosporiosis Caused by Scedosporium dehoogii in a Psoriatic Patient - Fang-Gu Li; Yan-Ping Yang; Wei Li; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2017)

Genetic diagnosis of a Chinese multiple endocrine neoplasia type 2A family through whole genome sequencing - Zhen-Fang Du; Peng-Fei Li; Jian-Qiang Zhao; Zhi-Lie Cao; Feng Li; Ju-Ming Ma; Xiao-Ping Qi (Journal of Biosciences, 2017)

A new putative alphapartitivirus recovered from the powdery mildew fungus Erysiphe palczewskii - Guihong Xiong; Ping Qiu; Cong Li; Zhuo Chen; Saif Ul Islam; Shouguo Fang; Zujian Wu; Songbai Zhang; Zhenguo Du (Virus Genes, 2017)

The mechanism of Jurkat cells apoptosis induced by Aggregatibacter actinomycetemcomitans cytolethal distending toxin - Hui-ping Chen; Lu Li; Xu Chen; Mi-fang Yang; Yu Ye; Xiao-qian Wang; Yan Xu (Apoptosis, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

The complete mitochondrial genome of the Burmese roofed turtle (Batagur trivittata) (Testudines: Geoemydidae) - Li Feng; Jiao Yang; Yan-Ping Zhang; Gui-Fang Zhao (Conservation Genetics Resources, 2017)

Di (2-ethylhexyl) phthalate impairs steroidogenesis in ovarian follicular cells of prepuberal mice - Fang-Nong Lai; Jing-Cai Liu; Lan Li; Jun-Yu Ma; Xue-Lian Liu; Yu-Ping Liu; Xi-Feng Zhang; Hong Chen; Massimo De Felici; Paul W. Dyce; Wei Shen (Archives of Toxicology, 2017)

In vitro reprogramming of rat bmMSCs into pancreatic endocrine-like cells - Hong-Tu Li; Fang-Xu Jiang; Ping Shi; Tao Zhang; Xiao-Yu Liu; Xue-Wen Lin; Zhong-Yan San; Xi-Ning Pang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

Synergistic and Superimposed Effect of Bone Marrow-Derived Mesenchymal Stem Cells Combined with Fasudil in Experimental Autoimmune Encephalomyelitis - Jing-Wen Yu; Yan-Hua Li; Guo-Bin Song; Jie-Zhong Yu; Chun-Yun Liu; Jian-Chun Liu; Hai-Fei Zhang; Wan-Fang Yang; Qing Wang; Ya-Ping Yan; Bao-Guo Xiao; Cun-Gen Ma (Journal of Molecular Neuroscience, 2016)

The complete mitogenome of a jumping spider Carrhotus xanthogramma (Araneae: Salticidae) and comparative analysis in four salticid mitogenomes - Wen-Yuan Fang; Zheng-Liang Wang; Chao Li; Xiao-Qing Yang; Xiao-Ping Yu (Genetica, 2016)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Polymorphisms in complement genes and risk of preeclampsia in Taiyuan, China - Weiwei Wu; Hailan Yang; Yongliang Feng; Ping Zhang; Shuzhen Li; Xin Wang; Tingting Peng; Fang Wang; Bingjie Xie; Pengge Guo; Mei Li; Ying Wang; et al. (Inflammation Research, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Effect of CO 2 on Chemical and Microbial Changes of Pacific White Shrimp During Modified Atmosphere Packaging - Yun-Fang Qian; Jing Xie; Sheng-Ping Yang; Wen-Hui Wu; Qing Xiong; Zhi-Li Gao; Jian-Bing Shi (Journal of Aquatic Food Product Technology, 2016)

Adenylate kinase: a novel antigen for immunodiagnosis and subunit vaccine against tuberculosis - Yangjiong Xiao; Wei Sha; Zhaofeng Tian; Yingying Chen; Ping Ji; Qin Sun; Huiyu Wang; Shujun Wang; Yong Fang; Han-Li Wen; Hui-min Zhao; Jie Lu; et al. (Journal of Molecular Medicine, 2016)

Identification of loci contributing to maize drought tolerance in a genome-wide association study - Nan Wang; Zhen-ping Wang; Xiao-ling Liang; Jian-feng Weng; Xiang-ling Lv; De-gui Zhang; Jie Yang; Hong-jun Yong; Ming-shun Li; Feng-hai Li; Li-yan Jiang; Shi-huang Zhang; et al. (Euphytica, 2016)

Empirical calibration of the clinopyroxene–garnet magnesium isotope geothermometer and implications - Wang-Ye Li; Fang-Zhen Teng; Yilin Xiao; Hai-Ou Gu; Xiang-Ping Zha; Jian Huang (Contributions to Mineralogy and Petrology, 2016)

The Effects of Molecular Properties on Ready Biodegradation of Aromatic Compounds in the OECD 301B CO2 Evolution Test - Mei He; Cheng-Fang Mei; Guo-Ping Sun; Hai-Bei Li; Lei Liu; Mei-Ying Xu (Archives of Environmental Contamination and Toxicology, 2016)

Mapping by sequencing in cotton (Gossypium hirsutum) line MD52ne identified candidate genes for fiber strength and its related quality attributes - Md. S. Islam; Linghe Zeng; Gregory N. Thyssen; Christopher D. Delhom; Hee Jin Kim; Ping Li; David D. Fang (Theoretical and Applied Genetics, 2016)

Seasonal variation of pheophorbide a and flavonoid in different organs of two Carpinus species and its correlation with immunosuppressive activity - Qianqian Sheng; Xianying Fang; Zunling Zhu; Wei Xiao; Zhenzhong Wang; Gang Ding; Linguo Zhao; Yujian Li; Ping Yu; Zhibin Ding; Qinru Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Controls of seed quantity and quality on seedling recruitment of smith fir along altitudinal gradient in southeastern Tibetan Plateau - Jing-sheng Wang; Ji-guang Feng; Bao-xiong Chen; Pei-li Shi; Jun-long Zhang; Jiang-ping Fang; Zhi-kai Wang; Shuai-chen Yao; Lu-bin Ding (Journal of Mountain Science, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

An Improved Solving Approach for Interval-Parameter Programming and Application to an Optimal Allocation of Irrigation Water Problem - Gaiqiang Yang; Ping Guo; Mo Li; Shiqi Fang; Liudong Zhang (Water Resources Management, 2016)

Serum Levels of Thioredoxin Are Associated with Stroke Risk, Severity, and Lesion Volumes - Meng-Hai Wu; Fang-Yu Song; Li-Ping Wei; Zhao-Yun Meng; Zhi-Qiang Zhang; Qin-De Qi (Molecular Neurobiology, 2016)

Neuroprotective Effects of β-Asarone Against 6-Hydroxy Dopamine-Induced Parkinsonism via JNK/Bcl-2/Beclin-1 Pathway - Sheng Zhang; Xue-Hong Gui; Li-Ping Huang; Min-Zhen Deng; Ruo-Ming Fang; Xue-Hong Ke; Yu-Ping He; Ling Li; Yong-Qi Fang (Molecular Neurobiology, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

The role of KCa3.1 channels in cardiac fibrosis induced by pressure overload in rats - Li-Mei Zhao; Li-Ping Wang; Hui-Fang Wang; Xiao-Zhen Ma; Dang-Xia Zhou; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2015)

Effects of miRNA-145 on airway smooth muscle cells function - Yun Liu; Xiuzhen Sun; Yuanyuan Wu; Ping Fang; Hongyang Shi; Jing Xu; Manxiang Li (Molecular and Cellular Biochemistry, 2015)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Mapping-by-sequencing of Ligon-lintless-1 (Li 1 ) reveals a cluster of neighboring genes with correlated expression in developing fibers of Upland cotton (Gossypium hirsutum L.) - Gregory N. Thyssen; David D. Fang; Rickie B. Turley; Christopher Florane; Ping Li; Marina Naoumkina (Theoretical and Applied Genetics, 2015)

Isolation of a new flavanone from Daidai fruit and hypolipidemic activity of total flavonoids extracts - Ling-Jun Zeng; Dan Chen; Qing-De Huang; Qun Huang; Yun-Fang Lian; Wei-Wei Cai; Hua-Ping Zeng; Yi-Li Lin (Natural Product Research, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

FaesPI, a Fagopyrum esculentum PISTILLATA ortholog, is involved only in stamen development - Zheng-Wu Fang; Xue-Ping Li; Xiao-Fang Li; Zhi-Xiong Liu (Journal of Plant Biology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Asymmetric dimethylarginine triggers macrophage apoptosis via the endoplasmic reticulum stress pathway - Dan Hong; Hai-Chao Gao; Xiang Wang; Ling-Fang Li; Chuan-Chang Li; Ying Luo; Kang-Kai Wang; Yong-Ping Bai; Guo-Gang Zhang (Molecular and Cellular Biochemistry, 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Next generation genetic mapping of the Ligon-lintless-2 (Li 2) locus in upland cotton (Gossypium hirsutum L.) - Gregory N. Thyssen; David D. Fang; Rickie B. Turley; Christopher Florane; Ping Li; Marina Naoumkina (Theoretical and Applied Genetics, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Profiles, sources, and transport of polycyclic aromatic hydrocarbons in soils affected by electronic waste recycling in Longtang, south China - De-Yin Huang; Chuan-Ping Liu; Fang-Bai Li; Tong-Xu Liu; Cheng-Shuai Liu; Liang Tao; Yan Wang (Environmental Monitoring and Assessment, 2014)

New eudesmane-type sesquiterpenoid from Solanum lyratum with cytotoxic activity - Xiu-Ping Nie; Fang Yao; Xi-Dian Yue; Gui-Sheng Li; Sheng-Jun Dai (Natural Product Research, 2014)

Ecological suitability assessment and introduction experiment on Rosa damascena trigintipetala in Sichuan Province, China - Xiao-lan Wang; Chun-jiang Su; Li Peng; Hai-e Wang; Hai-ming Wang; Wei Liu; Ping Li; Yan Fang (Journal of Mountain Science, 2014)

HMGB1 Contributes to Regeneration After Spinal Cord Injury in Adult Zebrafish - Ping Fang; Hong-Chao Pan; Stanley Li Lin; Wen-Qing Zhang; Heikki Rauvala; Melitta Schachner; Yan-Qin Shen (Molecular Neurobiology, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

The role of sucrose-metabolizing enzymes in pear fruit that differ in sucrose accumulation - Hu Ping Zhang; Ju You Wu; Gai Hua Qin; Gai Fang Yao; Kai Jie Qi; Li Fen Wang; Shao Ling Zhang (Acta Physiologiae Plantarum, 2014)

Assessing the contributions of lateral roots to element uptake in rice using an auxin-related lateral root mutant - Yu Liu; Erica Donner; Enzo Lombi; Renying Li; Zhongchang Wu; Fang-Jie Zhao; Ping Wu (Plant and Soil, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Influence of serum adiponectin level and SNP +45 polymorphism of adiponectin gene on myocardial fibrosis - Cheng-jun Yan; Su-mei Li; Qiang Xiao; Yan Liu; Jian Hou; Ai-fang Chen; Li-ping Xia; Xiu-chang Li (Journal of Zhejiang University-SCIENCE B, 2013)

Interactions between the P6 and P5-1 proteins of southern rice black-streaked dwarf fijivirus in yeast and plant cells - Jing Li; Jin Xue; Heng-Mu Zhang; Jian Yang; Ming-Fang Lv; Li Xie; Yuan Meng; Pei-Pei Li; Jian-Ping Chen (Archives of Virology, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

A new model for calculating the design wave height in typhoon-affected sea areas - Li-ping Wang; Baiyu Chen; Jian-fang Zhang; Zhengshou Chen (Natural Hazards, 2013)

A microsatellite-based genome-wide analysis of genetic diversity and linkage disequilibrium in Upland cotton (Gossypium hirsutum L.) cultivars from major cotton-growing countries - David D. Fang; Lori L. Hinze; Richard G. Percy; Ping Li; Dewayne Deng; Gregory Thyssen (Euphytica, 2013)

Spatial-temporal evolution pattern of agricultural productivity in northwestern sichuan plateau - Li Peng; Chun-jiang Su; Lian Sun; Ping Li; Yan Fang; Wei Liu; Xiao-lan Wang (Journal of Mountain Science, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Lack of effect of continuous glycyrrhizin administration on the pharmacokinetics of the P-glycoprotein substrate talinolol in healthy volunteers - Miao Yan; Ping-Fei Fang; Huan-De Li; Ping Xu; Yi-Ping Liu; Feng Wang; Hua-Lin Cai; Qin-You Tan (European Journal of Clinical Pharmacology, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Aggravated inflammation and increased expression of cysteinyl leukotriene receptors in the brain after focal cerebral ischemia in AQP4-deficient mice - Wen-Zhen Shi; Chun-Zhen Zhao; Bing Zhao; Qiao-Juan Shi; Li-Hui Zhang; Yan-Fang Wang; San-Hua Fang; Yun-Bi Lu; Wei-Ping Zhang; Er-Qing Wei (Neuroscience Bulletin, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Iridoids from the roots of Valeriana jatamansi and their biological activities - Jing Xu; Ping Guo; Yuanqiang Guo; Lingzhi Fang; Yushan Li; Zhanping Sun; Liping Gui (Natural Product Research, 2012)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Effects of drought stress on phosphorus and potassium uptake dynamics in summer maize (Zea mays) throughout the growth cycle - Ti-Da Ge; Ning-Bo Sun; Li-Ping Bai; Chen-Li Tong; Fang-Gong Sui (Acta Physiologiae Plantarum, 2012)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Neuroprotective properties of aucubin in diabetic rats and diabetic encephalopathy rats - Hong Yu Xue; Ya Nan Lu; Xue Mei Fang; Yong Ping Xu; Gui Zhen Gao; Li Ji Jin (Molecular Biology Reports, 2012)

Influence of UDP-glucuronosyltransferase polymorphisms on valproic acid pharmacokinetics in Chinese epilepsy patients - Xiao-Man Chu; Li-Fang Zhang; Guang-Ji Wang; Shen-Ning Zhang; Jia-Hui Zhou; Hai-Ping Hao (European Journal of Clinical Pharmacology, 2012)

Effects of different organic residues on rice yield and soil quality - Li Peng; Wei Liu; Chunjiang Su; Ping Li; Yan Fang; Xiaolan Wang; Lian Sun (Journal of Mountain Science, 2012)

Molecular biomarkers of colorectal cancer: prognostic and predictive tools for clinical practice - Wei-qin Jiang; Fang-fang Fu; Yang-xia Li; Wei-bin Wang; Hao-hao Wang; Hai-ping Jiang; Li-song Teng (Journal of Zhejiang University-SCIENCE B, 2012)

The evolution and utility of ribosomal ITS sequences in Bambusinae and related species: divergence, pseudogenes, and implications for phylogeny - HUI-XING SONG; SU-PING GAO; MING-YAN JIANG; GUANG-LI LIU; XIAO-FANG YU; QI-BING CHEN (Journal of Genetics, 2012)

A new sesquiterpene from endophytic fungus Aspergillus sp. - Shao-Liu Luo; Guo-Hong Li; Fang-Fang Liu; Li-Ping Lei; Zhen-Yuan Xia; Ke-Qin Zhang (Natural Product Research, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

A new ocotillol-type triterpenoid saponin from red American ginseng - Jin-Ping Liu; Fang Wang; Ping-Ya Li; Dan Lu (Natural Product Research, 2012)

The different expression of immune-related cytokine genes in response to velogenic and lentogenic Newcastle disease viruses infection in chicken peripheral blood - Wen-Quan Liu; Ming-Xing Tian; Yuan-Ping Wang; Yang Zhao; Nian-Li Zou; Fang-Fang Zhao; San-Jie Cao; Xin-Tian Wen; Ping Liu; Yong Huang (Molecular Biology Reports, 2012)

The −1123G>C Variant of PTPN22 Gene Promoter is Associated with Latent Autoimmune Diabetes in Adult Chinese Hans - Fang Liu; Jiang Liu; Tai-shan Zheng; Qing Li; Chen Wang; Xiao-ping Pan; Huijuan Lu; Yu-wu Zhao (Cell Biochemistry and Biophysics, 2012)

Involvement of KATP/PI3K/AKT/Bcl-2 Pathway in Hydrogen Sulfide-induced Neuroprotection Against the Toxicity of 1-methy-4-phenylpyridinium Ion - Xiao-Qing Tang; Yuan-Yuan Zhuang; Li-Li Fan; Heng-Rong Fang; Cheng-Fang Zhou; Ping Zhang; Bi Hu (Journal of Molecular Neuroscience, 2012)

Enhancement of succinic acid production by osmotic-tolerant mutant strain of Actinobacillus succinogenes - Xiaojiang Fang; Jian Li; Xiaoyu Zheng; Yonglan Xi; Kequan Chen; Ping Wei; PingKai Ouyang; Min Jiang (World Journal of Microbiology and Biotechnology, 2011)

Central nervous system regulation of food intake and energy expenditure: role of galanin-mediated feeding behavior - Peng-Hua Fang; Mei Yu; Yin-Ping Ma; Jian Li; Yu-Mei Sui; Ming-Yi Shi (Neuroscience Bulletin, 2011)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

The Activation of NMDA Receptor–ERK Pathway in the Central Amygdala is Required for the Expression of Morphine-Conditioned Place Preference in the Rat - Fang Li; Xiao-Sheng Wang; Ru-Ping Dai; Jian-Yi Zhang; Xin-Fu Zhou; Wei Hao; Chang-Qi Li (Neurotoxicity Research, 2011)

Usefulness of Enhanced Power Doppler Imaging in Monitoring Acral Microcirculation in Type 2 Diabetes Mellitus and its Complications - Fang Ma; Baozhen Zhao; Huiping Zhang; Wei-Ping Li; Yuan-Yuan Liu; Yuan-Yuan Dang; Rong Wu; Le Hang Guo; Chen Lu (Cell Biochemistry and Biophysics, 2011)

Occurrence and transmission of class 1 and 2 integrons among phenotypic highly ampicillin-resistant avian Escherichia coli isolates from Pakistan - Muhammad Yaqoob; Li Ping Wang; Tang Fang; Cheng-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Estimation of cancer cases and deaths attributable to infection in China - Wang Xiang; Ju-Fang Shi; Ping Li; Jian-Bing Wang; Li-Na Xu; Wen-Qiang Wei; Fang-Hui Zhao; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

Detection of hepatitis C virus by an improved loop-mediated isothermal amplification assay - Jin Yang; Mei-xin Fang; Jie Li; Guo-qiang Lou; Hang-jun Lu; Nan-ping Wu (Archives of Virology, 2011)

Effects of the crude extract of Polygala tenuifolia Willd on human sperm in vitro - Yi Qiu; Lei-guang Wang; Yi-fang Jia; Dan-tong Yang; Mei-hua Zhang; Yan-ping Zhang; Li-hong Zhang; Ling Gai (Journal of Zhejiang University-SCIENCE B, 2011)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Trichodermanin A, a novel diterpenoid from endophytic fungus culture - Pei-Xin Sun; Cheng-Jian Zheng; Wen-Chao Li; Gui-Lin Jin; Fang Huang; Lu-Ping Qin (Journal of Natural Medicines, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Isolation and Identification of a Pathogen of Silkworm Bombyx mori - Heng-Ping Tao; Zhong-Yuan Shen; Feng Zhu; Xiao-Fang Xu; Xu-Dong Tang; Li Xu (Current Microbiology, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Development and application of an efficient virus-induced gene silencing system in Nicotiana tabacum using geminivirus alphasatellite - Chang-jun Huang; Tong Zhang; Fang-fang Li; Xin-yue Zhang; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

Comparative analysis of rotifer community structure in five subtropical shallow lakes in East China: role of physical and chemical conditions - Xin-Li Wen; Yi-Long Xi; Fang-Ping Qian; Gen Zhang; Xian-Ling Xiang (Hydrobiologia, 2011)

Petrology and metamorphism of khondalites from the Jining complex, North China craton - Fang Wang; Xu-Ping Li; Hang Chu; Guochun Zhao (International Geology Review, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

High-mobility group box 1 exacerbates concanavalin A-induced hepatic injury in mice - Quan Gong; Hui Zhang; Jun-hua Li; Li-hua Duan; Shan Zhong; Xiao-ling Kong; Fang Zheng; Zheng Tan; Ping Xiong; Gang Chen; Min Fang; Fei-li Gong (Journal of Molecular Medicine, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Genetic analysis revealed LX4 genotype strains of avian infectious bronchitis virus became predominant in recent years in Sichuan area, China - Nian-Li Zou; Fang-Fang Zhao; Yuan-Ping Wang; Ping Liu; San-Jie Cao; Xin-Tian Wen; Yong Huang (Virus Genes, 2010)

Remote chlorophyll- a retrieval in Case-II waters using an improved model and IRS-P6 satellite data - Jing-Ping Xu; Fang Li; Bai Zhang; Xing-Fa Gu; Tao Yu (International Journal of Remote Sensing, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Effect of enalapril on plasma homocysteine levels in patients with essential hypertension - Fang-fang Fan; Yong Huo; Xu Wang; Xin Xu; Bin-yan Wang; Xi-ping Xu; Jian-ping Li (Journal of Zhejiang University-SCIENCE B, 2010)

Chromosomal localization of rDNA genes and genomic organization of 5S rDNA in Oreochromis mossambicus, O. urolepis hornorum and their hybrid - Hua Ping Zhu; Mai Xin Lu; Feng Ying Gao; Zhang Han Huang; Li Ping Yang; Jian Fang Gui (Journal of Genetics, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Induction and origin of adventitious roots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Shi-Jie Chai; Li-Ping Chen; Ming-Fang Zhang; Jing-Quan Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Viral infection of tobacco plants improves performance of Bemisia tabaci but more so for an invasive than for an indigenous biotype of the whitefly - Jian Liu; Meng Li; Jun-min Li; Chang-jun Huang; Xue-ping Zhou; Fang-cheng Xu; Shu-sheng Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

A new screening method based on yeast-expressed human dipeptidyl peptidase IV and discovery of novel inhibitors - Chen-Xi Hu; Hui Huang; Li Zhang; You Huang; Zhu-Fang Shen; Ke-Di Cheng; Guan-Hua Du; Ping Zhu (Biotechnology Letters, 2009)

Effect of CO2 enrichment on the glucosinolate contents under different nitrogen levels in bolting stem of Chinese kale (Brassica alboglabra L.) - Gui-xiao La; Ping Fang; Yi-bo Teng; Ya-juan Li; Xian-yong Lin (Journal of Zhejiang University-SCIENCE B, 2009)

A semi-supervised learning based method: Laplacian support vector machine used in diabetes disease diagnosis - Jiang Wu; Yuan-Bo Diao; Meng-Long Li; Ya-Ping Fang; Dai-Chuan Ma (Interdisciplinary Sciences: Computational Life Sciences, 2009)

Association of polymorphisms at restriction enzyme recognition sites of apolipoprotein B and E gene with dyslipidemia in children undergoing primary nephrotic syndrome - Peng Hu; Yuan Han Qin; Cheng Xue Jing; Feng Ying Lei; Ping Chen; Ming Fang Li (Molecular Biology Reports, 2009)

Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Nitrogen losses from integrated rice–duck and rice–fish ecosystems in southern China - Li Cheng-fang; Cao Cou-gui; Wang Jin-ping; Zhan Ming; Yuan Wei-ling; Shahrear Ahmad (Plant and Soil, 2008)

Triptolide protects against 1-methyl-4-phenyl pyridinium-induced dopaminergic neurotoxicity in rats: Implication for immunosuppressive therapy in Parkinson’s disease - Jun-Peng Gao; Shan Sun; Wen-Wei Li; Yi-Ping Chen; Ding-Fang Cai (Neuroscience Bulletin, 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Genetic Diversity and Systematic Evolution of Chinese Domestic Ducks Along the Yangtze-Huai River - Tang-jie Zhang; Hui-fang Li; Kuan-wei Chen; Hong Chang; Qing-ping Tang; Jing-xin Zhang (Biochemical Genetics, 2007)

Membrane Tension Modulates the Effects of Apical Cholesterol on the Renal Epithelial Sodium Channel - Shi-Peng Wei; Xue-Qi Li; Chu-Fang Chou; You-You Liang; Ji-Bin Peng; David G. Warnock; He-Ping Ma (The Journal of Membrane Biology, 2007)

Genomic analysis of a Chinese isolate of Getah-like virus and its phylogenetic relationship with other Alphaviruses - Jin-Sheng Wen; Wen-Zhong Zhao; Jian-Wei Liu; Hong Zhou; Jian-Ping Tao; Hui-Jun Yan; Yu Liang; Jing-Jiao Zhou; Li-Fang Jiang (Virus Genes, 2007)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Successful tubes treatment of esophageal fistula - Ning Zhou; Wei-xing Chen; You-ming Li; Zhun Xiang; Ping Gao; Ying Fang (Journal of Zhejiang University-SCIENCE B, 2007)

Generation of genetic engineering monoclonal antibodies against prion protein - Yin-Xia Huang; Jun Han; Chen-Fang Dong; Li Sun; Chen Gao; Xiao-Fan Wang; Lu Han; Wei Zhou; Bao-Yun Zhang; Hui-Ying Jiang; Mi-Fang Liang; Xiao-Ping Dong (Medical Microbiology and Immunology, 2007)

Response of soil respiration to simulated N deposition in a disturbed and a rehabilitated tropical forest in southern China - Jiangming Mo; Wei Zhang; Weixing Zhu; Yunting Fang; Dejun Li; Ping Zhao (Plant and Soil, 2007)

Repair of glutamate-induced excitotoxic neuronal damage mediated by intracerebroventricular transplantation of neural stem cells in adult mice - Juan Ma; Li-Jian Yu; Run-Di Ma; Yong-Ping Zhang; Juan-Zhi Fang; Xiao-Yu Zhang; Ting-Xi Yu (Neuroscience Bulletin, 2007)

Haplotype Frequency Distribution and Linkage Disequilibrium Analysis of Single Nucleotide Polymorphisms at the Human FMO3 Gene Locus - Da-Cheng Hao; Jie Sun; Bjarte Furnes; Daniel Schlenk; Zhen-Fang Hou; Ya-Ping Zhang; Sheng-Li Yang; Ling Yang (Biochemical Genetics, 2006)

Dynamics of vascular volume and hemodilution of lactated Ringer’s solution in patients during induction of general and epidural anesthesia - Yu-hong Li; Xian-feng Lou; Fang-ping Bao (Journal of Zhejiang University-SCIENCE B, 2006)

Seasonal Variation of Virioplankton in a Eutrophic Shallow Lake - Yan-Ming Liu; Qi-Ya Zhang; Xiu-Ping Yuan; Zheng-Qiu Li; Jian-Fang Gui (Hydrobiologia, 2006)

Land-cover changes in an urban lake watershed in a mega-city, Central China - Yan Li; Shuqing Zhao; Kun Zhao; Ping Xie; Jingyun Fang (Environmental Monitoring and Assessment, 2006)

A genetic diversity comparison between captive individuals and wild individuals of Elliot’s Pheasant (Syrmaticus ellioti) using mitochondrial DNA - Ping-ping Jiang; Qiu-lei Lang; Sheng-guo Fang; Ping Ding; Li-ming Chen (Journal of Zhejiang University-SCIENCE B, 2005)

Fast screening target sites for RNA interference using a cell-free system - Huang Mei; Jia Fang-Jun; Li Chong-Yong; Li Yi-Ping; Guo Li-He (Biotechnology Letters, 2005)

Production of interspecific somatic hybrids between tuber mustard (Brassica juncea) and red cabbage (Brassica oleracea) - Li-Ping Chen; Ming-Fang Zhang; Chun-Shun Li; Yutaka Hirata (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Estimation of ocean primary productivity and its spatio-temporal variation mechanism for East China Sea based on VGPM model - Guosheng Li; Ping Gao; Fang Wang; Qiang Liang (Journal of Geographical Sciences, 2004)

Plant Regeneration from Hypocotyl Protoplasts of Red Cabbage (Brassica Oleracea) by Using Nurse Cultures - Li-Ping Chen; Ming-Fang Zhang; Qiu-Bing Xiao; Jian-Guo Wu; Yutaka Hirata (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)

A study on cellular automata based on relational databases and spatio-temporal simulations of culture diffusion - Ping Luo; Qing-yun Du; Su-fang He; Sen Li; Gallagher Michael; Hui-en Niu (Chinese Geographical Science, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

An ultra-metastatic model of human colon cancer in nude mice - Fang X. Sun; Aaron R. Sasson; Ping Jiang; Zili An; Reza Gamagami; Lingna Li; A.R. Moossa; Robert M. Hoffman (Clinical & Experimental Metastasis, 1999)

Effect of total alkaloid ofPeganum harmala L. in the treatment of experimental haemosporidian infections in cattle - Bingtang Fan; Jilan Liang; Jucheng Men; Fang Gao; Guangling Li; Sixi Zhao; Tingjun Hu; Ping Dang; Ling Zhang (Tropical Animal Health and Production, 1997)